Blind prediction of slope safety factors using machine learning - Fu-Hsuan Yeh; Wei Liang; Louis Ge; Cheng-Hsi Hsiao (European Journal of Environmental and Civil Engineering, 2026)

Degradation of mycotoxins in cow milk by dielectric barrier discharge cold plasma and its effect on milk quality - Yike Han; Shangchen Fu; Meng Li; Siqi Wang; Yijie Lu; Wupeng Ge; Chunfeng Guo; Yuan Zhou; Zhenpeng Gao (International Dairy Journal, 2026)

Facet-regulated Ni/TiO2 interfacial configurations for hydrothermal cellulose methanation - Lijun Xue; Mengli Zhou; Xinyu Liu; Juan Fu; Huaiyun Ge; Xin Tu; Qiying Liu; Jianchun Jiang (Chemical Engineering Journal, 2026)

Apatite geochemistry of granites from the Xiaolonghe Tin deposit, Western Yunnan: Implications for petrogenesis and mineralization - Kun Ge; Xiang Sun; Yong Fu; Yaqi Ye; Yingjie Wang; Xianyi Huang; Xiaobo Si; Mingjun Zheng (Journal of Geochemical Exploration, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Urbanization drives rapid convergence of riverine greenhouse gas levels in the urban agglomeration, North China - Ling Wen; Zhengkui Ge; Yulin Qi; Dietrich A. Volmer; Chao Ma; Chunmei Chen; Zhifeng Yan; Pingqing Fu; Si-Liang Li (Agriculture, Ecosystems & Environment, 2026)

Interpretable and robust machine-learning prediction of CO2-H2O-coal wettability for deep CO2-enhanced coalbed methane and geological storage - Yunzhong Jia; Chenying Yu; Zhaolong Ge; Jiren Tang; Xiao Sun; Wenyu Fu (Gas Science and Engineering, 2026)

High thermoelectric performance in Sm and Bi dual-doped GeTe with nuanced recrystallization annealing - Ge Fu; Shangchao Lin; Yixuan Liu; Yang Liu; Qilin Zhang; Jie Xiao; Changying Zhao (Chemical Engineering Journal, 2026)

Bacillus subtilis exopolysaccharide enhances Lactobacillus johnsonii-kynurenic acid to restore intestinal T helper 17/regulatory T cell balance via aryl hydrocarbon receptor - Ge Zhang; Li Cao; Gang zhang; Rongrong Fu; Yujun Wu; Jinbiao Zhao; Zeyu Zhang (Carbohydrate Polymers, 2026)

An analytical model for liquefaction-induced underground buried structure uplift with experimental validation - Fu-Hsuan Yeh; Chun-Yu Hsu; Louis Ge; Siau Chen Chian (Tunnelling and Underground Space Technology, 2026)

Urinary biomarkers of emerging contaminants in relation to prevalent Parkinson's disease: An exploratory mixture and network toxicology study - Chiqun Shan; Yiming Ge; Junye Bian; Yuli Lin; Bo Fu; Qinru Xiao; Aihua Guo; Mengyan Li; Pan Xu; Yi Chen; Haobo Chen; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Functional differentiation of active hydrogen on Pd/Cu catalysts for efficient electrocatalytic nitrate reduction to ammonia - Chunhong Fu; Chaohui Zhang; Jiangli Sun; Huizhong Wu; Ge Song; Minghua Zhou (Journal of Hazardous Materials, 2026)

Alkali-triggered kinetic matching of polymerization and crosslinking enables hydrogels with programmable mechanics, flexible sensing, and dynamic information encryption - Hongyan Cao; Shengwei Fu; Yaqing Ge; Xueting Yang; Xiaoli Wang; Xianglei Zhao; Yanyan Zhao; Xiangling Gu (Chemical Engineering Journal, 2026)

Interplay of quorum-sensing signals (homoserine lactone/penicillic acid) and nitrate in regulating microbial processes: As(III) immobilization, CH4 and N2O emission in constructed wetlands - Dongxue Fu; Huiwen Ma; Jing Zhang; Honghui Wang; Yixin Wu; Liyun Ge; Chunzhen Fan; Shuqing Wu; Shuyun Zhang; Hui Gao; Zheng Chen (Bioresource Technology, 2026)

Expression and Functional Characterisation of EhSWP 26 in Ecytonucleospora hepatopenaei : Insights From RNA Interference and Subcellular Localisation Analyses - Huiwen Jiang; Xiaohui Cao; Yi Qiao; Tingyue Liu; Jie Cheng; Ge Jiang; Xianping Fan; Haibo Wang; Kuipeng Fu; Hui Shen (Journal of Fish Diseases, 2026)
Ecytonucleospora hepatopenaei (EHP) is an obligate intracellular microsporidian that causes severe growth retardation in Penaeus vannamei (P. vannamei ), yet its pathogenic mechanisms remain incompletely clear. As the spore wall is essential for resisting environmental stress and mediating host invasion, characterising its protein components is critical for elucidating EHP biology. In this study, we identified and cloned a novel spore wall protein, EhSWP26. Sequence analysis revealed that EhSWP26 contains a 687 bp open reading frame encoding a 228‐amino‐acid polypeptide, lacking a signal peptide and transmembrane domain but harbouring a conserved MICSWaP (Microsporidia Spore Wall and Associated Proteins) domain characteristic of the microsporidian MICSWaPs family. Immunoelectron microscopy and indirect immunofluorescence assays demonstrated that EhSWP26 localises to the mature spore wall, where it is distributed in both the exospore and endospore layers. RNA interference further confirmed that silencing EhSWP26 significantly reduced its transcript level and led to a marked decrease in EHP spore load in shrimp hepatopancreas. Collectively, these findings indicate that EhSWP26 is a key structural and functional component associated with spore wall formation and host infection, likely playing an essential role in the EHP life cycle. This study enhances our understanding of EHP spore wall composition and function, provides a foundation for investigating its proliferation and infection mechanisms, and highlights EhSWP26 as a promising target for diagnostic development and therapeutic intervention in EHP disease of P. vannamei .

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Macro-micro integrated offshore wind farm siting using interval-valued spherical fuzzy Z-numbers - Xiaolin Ge; Yiwei Huang; Yang Fu; Ruanming Huang; Yaoliang Zhu; Wei Xie; Tianyi Chen (Ocean Engineering, 2026)

KLF4/FOXF1 axis alleviates silicosis fibrosis by modulating fibroblast behavior and extracellular matrix remodeling - Xuesong Zhang; Hui Fan; Ge Qin; Bowen Fu; Botao Hu; Jingwen Fan; Youliang Zhao; Yuanmeng Qi; Xueyang Zhang; Wu Yao; Changfu Hao (Journal of Environmental Sciences, 2026)

Co-evolution of the pangenome, mobile genetic elements, and antimicrobial resistance genes reveals the public health risks of the dominant Salmonella 4,[5],12:i:- ST34 clone - Jiawen Chen; Shuaicheng Wu; Laiyu Fu; Yan Li; Xiaoxiao Duan; Yanling Liu; Yichi Zhang; Xindong Ge; Yongda Zhao; Lili Guo (Food Research International, 2026)

PAK2 mediates PhIP-induced proliferative and oxidative stress responses in colorectal cancer cells - Zeli Li; Dongxu Xie; Wang Tao; Xinyan Wu; Ge Zhang; Jiarui Nicole Fu; Shuwen Li; Shanshan Cai (Chemico-Biological Interactions, 2026)

Corrigendum to “Interplay of quorum-sensing signals (homoserine lactone/penicillic acid) and nitrate in regulating microbial processes: As(III) immobilization, CH4 and N2O emission in constructed wetlands” [Biores. Technol. 455 (2026) 134788] - Dongxue Fu; Wenhui Ma; Jing Zhang; Honghui Wang; Yixin Wu; Liyun Ge; Chunzhen Fan; Shuqing Wu; Shuyun Zhang; Hui Gao; Zheng Chen (Bioresource Technology, 2026)

Synergistic Interactions Between Warming and Elevated Atmospheric CO 2 Increase Soil Organic Carbon Sequestration - Ruiqi Yao; Yike Zhang; Wolfgang Wanek; Zhongkui Luo; Haoran Fu; Scott X. Chang; Cesar Terrer; Mingkai Jiang; Tida Ge; Guopeng Liang; Yuanhe Yang; Yiqi Luo; et al. (Global Change Biology, 2026)
Warming and elevated CO 2 (eCO 2 ) are two potentially opposing climate‐carbon (C) feedback mechanisms that modulate the magnitude of the land C sink, with warming decreasing and eCO 2 increasing C sequestration. However, their net effect on soil organic C (SOC)—the largest terrestrial C stock—remains uncertain. Here, we quantify how warming, eCO 2 , and their interactions influence SOC by using 5558 paired observations from 1392 global studies across ecosystem types. Our study shows that warming reduces SOC by 8.0%, primarily by suppressing aboveground C inputs (−1.0%) and decreasing microbial C use efficiency (−9.9%). Concurrent warming and eCO 2 increase SOC by 7.6%—a synergistic effect larger than eCO 2 alone (+4.8%), primarily contributed by croplands. This outcome may result from increases in plant C inputs and soil nitrogen availability under eCO 2 , which facilitate microbial C assimilation and necromass formation (+3.9%). These processes promote the accumulation of mineral‐associated C (+9.9%) and offset the negative effects of warming. The combined effect of warming and eCO 2 is projected to increase SOC by 27.4 Pg C by 2100. Our findings highlight that synergistic interaction between warming and eCO 2 increases SOC sequestration and enhances SOC stability under future climate change.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dual and concentration-dependent effects of SO2 on gas adsorption, diffusion, and storage performance in anthracite - Wenyu Fu; Yiyu Lu; Xinguo Yang; Yunzhong Jia; Zhaolong Ge; Jiaqi Yi; Yifan Liu (Journal of Environmental Chemical Engineering, 2026)

A multi-scale fracture prediction method based on improved deep embedded clustering - Yu-jia Lu; Chao Chen; Zhu-jiang Liu; Fu-bin Wei; Zhe-ge Liu (Applied Geophysics, 2026)

Docosahexaenoic acid alleviates Ornidazole toxicity related to spermatogenic dysfunction by modulating PPARγ-dependent ER-mitochondrial uncoupling - Chuwei Li; Shanmeizi Zhao; Chongli Shi; Shanshan Sun; Zhaowanyue He; Yao Xu; Lu Zheng; Ting Tang; Shengjie Qiu; Kuan Liang; Hong Zhang; Zhichuan Zou; et al. (Science China Life Sciences, 2026)

Data Fusion Framework for a High-Resolution Regional Dataset in the Western North Pacific - Lifu Fu; Chunling Zhang; Yijun Ge; Bo Shu; Ruoxiao Zhou (Journal of Marine Science and Engineering, 2026)
Based on the large volume of observational data obtained from Argo and several satellites, an increasing number of datasets are being developed and applied to oceanographic research. However, there are still problems such as sparse subsurface observations, insufficient parameters, and weak pertinence. This study provides a basic framework for high-resolution data fusion that focuses on the multi-source observations in the Western North Pacific. Multi-source observations from satellites, Argo floats, and historical in situ profiles are fused using a statistical model and a gradient-dependent optimal interpolation method. A daily gridded dataset with a 0.25° horizontal resolution is developed, which includes temperature, salinity, and currents. The results show that the correlation coefficients between the observations and the inverted profiles of temperature and salinity are about 0.99 and 0.94, respectively, with mean root mean square errors of about 1.27 °C and 0.13, respectively. In the Northwest Pacific Ocean, the most suitable parameter settings are a search radius of 1.5° in longitude and latitude, correlation scale constant of 0.25°, and relative observation error of 2. Consequently, the average RMSEs of the fused temperature and salinity fields are 0.43°C and 0.056, respectively. Compared with other reanalysis datasets, the product constructed in this study retains more high-frequency ocean signals, and its temperature error relative to XBT observations is also the smallest. Furthermore, the dataset effectively depicts the characteristics of marine dynamic processes such as the Kuroshio paths and mesoscale eddies.

An MPC-ECMS Integrated Energy Management Strategy for Shipboard Gas Turbine–Photovoltaic–Hybrid Energy Storage Power Systems - Zhicheng Ye; Zemin Ding; Jinzhou Fu; Ge Xia (Journal of Marine Science and Engineering, 2026)
A real-time optimized model predictive control–equivalent consumption minimization strategy (MPC-ECMS) is proposed for the energy management of shipboard gas turbine–photovoltaic hybrid energy storage (GT-PV-HESS) power systems. Different from conventional MPC-ECMS methods that only adopt single-level SOC-based feedback regulation, the strategy aims to overcome the limitations of conventional methods, including the poor adaptability of rule-based strategies and the lack of foresight in traditional ECMS, which cannot achieve simultaneous improvements in fuel economy, generation efficiency, and battery lifespan while maintaining system stability under dynamic operating conditions. The proposed strategy integrates the forward-looking optimization ability of MPC and the real-time decision-making advantage of ECMS. MPC is used to predict short-term load and photovoltaic power and identify operating modes, and a two-level equivalent factor adjustment mechanism is designed based on predicted conditions and battery state of charge (SOC). The optimized factor is applied in ECMS to achieve optimal power allocation between the gas turbine and battery under system constraints, while the supercapacitor implements power secondary correction to suppress bus voltage fluctuations caused by gas turbine operation. The architectural novelty lies in the two-level coordination mechanism and the marine-oriented hybrid energy storage cooperation. Simulation studies are conducted on the MATLAB/Simulink R2021b platform, and the results validate that it yields superior performance to the rule-based control and traditional ECMS under typical ship operating conditions. It increases gas turbine efficiency to 15.62% (0.47% and 6.24% higher than the two conventional methods). Over the 120 s simulation period, the proposed strategy reduces total fuel consumption to 1.049 kg, which is lower than 1.054 kg for the rule-based strategy and 1.192 kg for conventional ECMS. The battery SOC fluctuation is restricted to only 3.89%. The maximum DC bus voltage fluctuation rate is controlled within 3.28%, which meets the stability requirements of shipboard DC microgrids. The proposed strategy achieves a comprehensive and superior balance among fuel economy, power generation efficiency, and battery life while ensuring stable system operation under all working conditions. This two-level MPC-ECMS framework provides a high-performance and practically feasible energy management solution for shipboard hybrid power systems.

Simultaneous analysis of long-chain alkenones and chlorophyll derivatives offers new insights into the ecology of Isochrysis algae in the Holocene Black Sea - Olawale O. Alo; Junpeng Fu; Wenshuo Zhao; Yi Ge Zhang; Yongsong Huang; Xiao-Lei Liu (Marine Chemistry, 2026)

Comparative evaluation of urine, whole blood, and serum as biological matrices for human biomonitoring of neonicotinoid insecticides and metabolites - Yuli Lin; Junye Bian; Kai Lin; Yiming Ge; Chiqun Shan; Bo Fu; Weizhong Chen; Tao Chen; Qinru Xiao; Bingjun Lu; Qunlin Xiao; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Machine learning prediction of CO2-water-coal wettability with SHAP-based interpretability and field validation - Yunzhong Jia; Chenying Yu; Zhaolong Ge; Yiyu Lu; Yifan Liu; Wenyu Fu (International Journal of Coal Geology, 2026)

A framework approach for analyzing water transformation characteristics of typical watersheds in arid zones during irrigation periods - Jingming Liu; Jianli Ding; Jinjie Wang; Zhe Zhang; Jie Zou; Zipeng Zhang; Xiao Wang; Zan Fu; Xiangyu Ge (Environmental Modelling & Software, 2026)

Knowledge-embedded deep reinforcement learning for real-time dispatch of wind-solar-hydro hybrid generation systems - Yuanyu Ge; Jun Xie; Shuo Feng; Jiaqi Chang; Denghui Fu (Journal of Cleaner Production, 2026)

Interactions of carbon‑nitrogen coupling in the Agro-Pastoral Ecotone of Northern China - Shijun Tu; Wanfa Wang; Cai Li; Yuanbi Yi; Jinfeng Ge; Wenrui Yao; Wenhong Shi; Fu-Jun Yue; Zhongjun Wang; Yulin Qi; Si-Liang Li (CATENA, 2026)

Molecular identification and genetic diversity of Echinococcus granulosus sensu stricto in livestock from Qinghai lake on the Qinghai-Tibetan plateau - Jun He; Guoyan Zhou; Fan Zhang; Hongrun Ge; Ao Chen; Ru Meng; Zhihong Guo; Yijuan Ma; Yong Fu (Veterinary Research Communications, 2026)

Analysis of the sources of rare earth elements in deep groundwater of the Huainan Coalfield based on the ACPS-MLR model - Jiawen Chen; Tao Jiang; Qingsong Ge; Tianqi Ma; Jiyang Zhao; Liugen Zheng; Xianjie Fu; Shaoneng Du (Environmental Geochemistry and Health, 2026)

Ultimate Axial Load Capacity of Production Tubular Strings in Offshore Extended-Reach Wells - Yanfei Li; Bin Cai; Junrui Ge; Hao Fu; Jian Wu; Penglei Tang; Lei Zuo; Zhengkang Li; Shuhan Liu; Guangming Fu (Journal of Marine Science and Engineering, 2026)
As oil and gas exploration advances, tubular strings in extended-reach wells are becoming increasingly susceptible to buckling, self-locking, and other failure modes due to their relatively low weight and limited structural stiffness. Existing studies have mainly focused on running feasibility and associated mechanical responses, whereas systematic investigations of the ultimate axial load capacity of deployed tubular strings remain limited. To address this research gap, the present study investigates the ultimate axial load capacity of tubular strings in deepwater extended-reach wells, explicitly accounting for the constitutive behavior of the tubular material. Numerical simulations were performed under both tensile and compressive loading conditions for different well trajectories, dogleg severities, material grades, and wellbore diameters, and the effects of these factors on the ultimate axial load capacity were systematically evaluated. The numerical predictions at the initial yielding stage were compared with available analytical solutions, and good agreement was obtained, indicating that the proposed model is reliable for initial yield analysis. The results show that well trajectory, dogleg severity, material grade, and wellbore diameter significantly influence the ultimate axial load capacity of tubular strings. The findings of this study provide useful guidance for structural integrity assessment, design optimization, and operating-parameter selection for downhole tubular strings in deepwater and ultra-deepwater oil and gas developments, thereby supporting the safe and efficient completion of extended-reach wells.

Soil science research in Research Center for Eco-Environmental Sciences: Review and outlook - Baodong Chen; Zhipeng Hao; Lei Luo; Nan Wu; Wenju Liu; Dong Zhu; Yuan Ge; Weiping Chen; Wentao Jiao; Xin Zhang; Siyi Liu; Jupei Shen; et al. (Journal of Environmental Sciences, 2026)

Research on multi-physics field collaborative detection methods for concealed fire zones: Based on variable-temperature magnetic-dielectric-resistive characteristics - Xiaokun Zhao; Jun Ge; Wencai Wang; An Zhang; Yuhua Bai; Yong Liu; Weixia Fu (Journal of Applied Geophysics, 2026)

Supercritical CO2 induced development of macropores/fractures in coal and associated mineral precipitation - Yudong Hou; Caiyun Xiao; Wenyu Fu; Wenrui Liu; Yunzhong Jia; Zhaolong Ge (International Journal of Greenhouse Gas Control, 2026)

Ecological effects and strategies of Spartina alterniflora Loisel. removal in China - Zhanbin Luo; Fu Chen; Xi-En Long; Jing Ma; Jiyou Wei; Yudi Guo; Yanfeng Zhu; Yongjun Yang; Xiaoping Ge; Yanyan Kang; Ming Zou; Lei Liu; et al. (Environmental Impact Assessment Review, 2026)

Dipole-engineered pyridinium iodide passivation for efficient Sn-Pb and all-perovskite tandem solar cells - Ciyu Ge; Chenwei Ni; Qi Xu; Bokai Hao; Wei Ai; Chengjie Deng; Peiyan Zhang; Xinzhi Zu; Hongyan Lu; Zeyu Zhang; Weijun Ke; Haisheng Song; et al. (Chemical Engineering Journal, 2026)

Metagenomic insights into species shifts and adaptation mechanisms of anammox communities treating incineration leachate - Da Kang; Yikai Zhao; Xinran Zhang; Xianyong Zeng; Xindi Fu; Bingxin Li; Zheng Ge; Liang Zhang; James P. Shapleigh; Yongzhen Peng (Chemical Engineering Journal, 2026)

Energy-efficient chlorine-mediated paired electrocatalysis for simultaneous H2O2 production and coal chemical wastewater purification - Jiana Jing; Yingying Du; Chunhong Fu; Jiangli Sun; Ge Song; Minghua Zhou (Journal of Hazardous Materials, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

From chemical oxidation to physical reconstruction: The depth-dependent wettability evolution in coal during CO2 geological sequestration - Yiyu Lu; Yifan Liu; Yunzhong Jia; Zhaolong Ge; Chenying Yu; Wenyu Fu (Chemical Engineering Journal, 2026)

Phytochemicals and health-promoting evaluations of Ophiorrhiza puffii , a chinese endemic plant - Qing Bu; Qi-Bin Yang; Zeng-Yue Ge; Ze-Xiong Shi; Lin-Fu Liang (Natural Product Research, 2026)

Insights into land deformation processes in the Yellow River Delta (China) from synthetic aperture radar interferometry time series and machine learning - Pengfei Ge; Mi Chen; Roberto Tomás; Hui Liu; Kailun Fan; Xi Cheng; Xingyuan Fu; Shuang Wang (Advances in Space Research, 2026)

Rainfall shapes CO₂ emission and dissolved organic matter dynamics in a karst catchment: Controlling factors revealed by isotopic and molecular signatures - Jinfeng Ge; Yulin Qi; Yuanbi Yi; Chao Ma; Wenrui Yao; Xin Liu; Haoyang Wang; Keyan Li; Fu-Jun Yue; Tao Peng; Si-Liang Li (Water Research, 2026)

Mechanisms of SO2 concentration-dependent pore evolution in anthracite during CO2 sequestration - Wenyu Fu; Yiyu Lu; Yunzhong Jia; Zhaolong Ge; Jiaqi Yi (Gas Science and Engineering, 2026)

Cyclic CO2/N2 injection enhances CO2 storage and CH4 recovery in anthracite by optimizing pore structure and competitive adsorption - Yunzhong Jia; Jiaqi Yi; Xinyu Wang; Zhaolong Ge; Wenyu Fu; Yiyu Lu; Caiyun Xiao (Gas Science and Engineering, 2026)

Biochar mitigates the suppressive effects of nitrogen deposition on soil methane uptake in a subtropical forest - Jiashu Zhou; Caixian Tang; Tony Vancov; Shenglei Fu; Yunying Fang; Tida Ge; Yanfei Dong; Yu Luo; Bing Yu; Yanjiang Cai; Jason C. White; Yongfu Li (Agriculture, Ecosystems & Environment, 2026)

Rainfall process-related dissolved organic carbon wet deposition at the southern foot of Qinling Mountain: Implications for atmospheric carbon budget at the boundary area between north and south China - Jie Zeng; Guilin Han; Qixin Wu; Lihong Fu; Qing Ma; Jie Zhang; Xinyi He; Xin Ge (Journal of Hydrology, 2025)

GRACE-derived spatiotemporal changes of terrestrial water storage in the major plateaus of China - Dong Wang; Bo-Hui Tang; Yingyun Li; Wei Fu; Zhitao Fu; Zhen Zhang; Zhongxi Ge (Global and Planetary Change, 2025)

An interface-engineered three-channel synapse using staggered transition metal dichalcogenides/ferroelectric heterojunctions - Yuqing Zhou; Qibin Zeng; Xingke Fu; Chao Yang; Feiyan Hou; Chen Ge; Kaiyang Zeng; Huajun Liu; Zheng Chai; Tai Min; Tao Li (Chemical Engineering Journal, 2025)

Uncovering interactive impacts of climate extremes and land use change on soil erosion using a coupled RUSLE-OPGD framework - Libo Ge; Hao Zheng; Zihao Fu; Chongfa Cai; Yujie Wei (CATENA, 2025)

Upregulation of NR2A in Glutamatergic VTA Neurons Contributes to Chronic Visceral Pain in Male Mice - Meng-Ge Li; Shu-Ting Qu; Yang Yu; Zhenhua Xu; Fu-Chao Zhang; Yong-Chang Li; Rong Gao; Guang-Yin Xu (Neuroscience Bulletin, 2025)
Chronic visceral pain is a persistent and debilitating condition arising from dysfunction or sensitization of the visceral organs and their associated nervous pathways. Increasing evidence suggests that imbalances in central nervous system function play an essential role in the progression of visceral pain, but the exact mechanisms underlying the neural circuitry and molecular targets remain largely unexplored. In the present study, the ventral tegmental area (VTA) was shown to mediate visceral pain in mice. Visceral pain stimulation increased c-Fos expression and Ca 2+ activity of glutamatergic VTA neurons, and optogenetic modulation of glutamatergic VTA neurons altered visceral pain. In particular, the upregulation of NMDA receptor 2A (NR2A) subunits within the VTA resulted in visceral pain in mice. Administration of a selective NR2A inhibitor decreased the number of visceral pain-induced c-Fos positive neurons and attenuated visceral pain. Pharmacology combined with chemogenetics further demonstrated that glutamatergic VTA neurons regulated visceral pain behaviors based on NR2A. In summary, our findings demonstrated that the upregulation of NR2A in glutamatergic VTA neurons plays a critical role in visceral pain. These insights provide a foundation for further comprehension of the neural circuits and molecular targets involved in chronic visceral pain and may pave the way for targeted therapies in chronic visceral pain.

Enhancing Laterite’s Mechanical Properties and Reducing Water Sensitivity with Glycerol Monostearate - Kun-Yu Fu; Yan-Ge Chen; Ying-Zhen Ji; Qi-Ya Wang (Geotechnical and Geological Engineering, 2025)

Selective kernel convolution with global attention mechanism for multitask change detection in optical and SAR images - Tonggen Yang; Liang Huang; Bo-Hui Tang; Zhitao Fu; Zhen Zhang; Zhongxi Ge; Man Zhang; Siming Pu (Earth Science Informatics, 2025)

Genetic mechanism of deep zeolite-rich reservoirs: a case study of the Lower Wuerhe Formation in Junggar Basin - Tianxin Hu; Yongqiang Qu; Jian Wang; Junjun Zhou; Wenfeng Ge; Chenyu Fu; Haiguang Wu (Frontiers of Earth Science, 2025)

Chitin nanofiber-stabilized pickering emulsions loaded with citrus essential oil: Characterization and application for pork preservation - Ge Wang; Te Yu; Jiran Lv; Linhua Huang; Ok-Hwan Lee; Xing Fu (Food Research International, 2025)

Structural modification of gelatin with four flavonoids for improving its properties - Kexin Fu; Jiangtao Li; Jing Ge; Yutong Zheng; Yaxin Sang; Guifang Tian (Food Chemistry, 2025)

Chlorine-anion doping enhances the metal-oxygen covalency of Bi0.5Sr0.5FeO3-δ air electrode: achieving superior catalytic activity for reversible solid oxide cells - Hui Ye; Zhipeng Miao; Yanfeng Fu; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng; Sheng Cui (Chemical Engineering Journal, 2025)

Microbial metabolisms determine soil priming effect induced by organic inputs - Yingyi Fu; Wanling Liu; Zhiyi Chen; Marc Redmile-Gordon; Chao Liang; Caixian Tang; Georg Guggenberger; Shaobin Yan; Liming Yin; Jingjing Peng; Lukas Van Zwieten; Peng Wang; et al. (Soil Biology and Biochemistry, 2025)

Nitrogen-containing pollutant records in rainfall from the north-south boundary area in China: Compositions, variations, and sources - Xinyi He; Jie Zeng; Qixin Wu; Qing Ma; Jie Zhang; Lihong Fu; Xin Ge (Process Safety and Environmental Protection, 2025)

Spatiotemporal evolution and factors influencing energy system resilience in China under the dual carbon target - Lingna Liu; Siyu Yao; Jianping Ge; Tongrong Fu; Yong Yan (Journal of Cleaner Production, 2025)

Consecutive wet deposition of nitrogen along half of China's coastal cities induced by Super Typhoon Muifa (2022) with multiple landfalls - Ying Zhang; Baozhu Ge; Guanghua Chen; Duo Wang; Feili Li; Joshua S. Fu; Xuejun Liu; Zifa Wang (Journal of Environmental Sciences, 2025)

Warming coupled with uranium exposure can alter the marine microbial community and induce toxin accumulation in shellfish - Ran-li Wang; Qian Fu; Ge Yao; Jin-long Lai; Shao-heng Bao; Xue-gang Luo; Hui Jiang; Yu Zhang; Peng-gang Han (Journal of Environmental Radioactivity, 2025)

Rainfall-driven heavy metals wet deposition in a typical small city at southern foothills of Qinling Mountains, the boundary zone of north and south China - Jie Zhang; Jie Zeng; Qixin Wu; Xin Ge; Xinyi He; Lihong Fu (Environmental Pollution, 2025)

Improved desertification grading and fine-scale integration of land use and severity for monitoring and ecological restoration at desert margins - Xuanqi Liu; Hengqian Zhao; Xiadan Huangfu; Ge Liu; Hao Yuan; Yujiao Zhang; Hancong Fu (Ecological Engineering, 2025)

Sources and potential health indicators in urban aerosols revealed by gas chromatography-mass spectrometry combined with nitrogen chemiluminescence detector: evidence from a megacity (Tianjin) of China - Jingying Ma; Yulin Qi; Yufu Han; Jinfeng Ge; Ling Wen; Xiaoli Fu; Wei Hu; Zongbo Shi; Dietrich A. Volmer; Pingqing Fu (Atmospheric Environment, 2025)

Chemotaxonomically significant phytochemicals with α-glucosidase and tyrosinase inhibitory activities from Chinese endemic plant Ophiorrhiza hunanica - Qing Bu; Qi-Bin Yang; Can-Qi Liu; Zeng-Yue Ge; Xiao-Wen Liao; Lei Wu; Lin-Fu Liang (Natural Product Research, 2025)

Deciphering the microbial mechanisms underlying glucose induced soil priming effects under low and high nutrient levels - Jiaqi Wang; Xichang Zhang; Yingyi Fu; Lukas Van Zwieten; Han Sun; Georg Guggenberger; Lingfei Hu; Yu Luo; Tida Ge; Yakov Kuzyakov (European Journal of Soil Biology, 2025)

Alkyl chain engineering in β-linked dimer acceptors: Balancing crystallinity and phase separation for high-performance organic photovoltaics - Yun Li; Jiawei Fu; Hang Jiang; Zhongwei Ge; Haisheng Ma; Yinuo Yang; Xiaobo Sun; Shouchun Yin (Chemical Engineering Journal, 2025)

Bio-based ion-conducting hydrogels with tunable mechanical and electralchemical properties via metal ion-regulated cellulose chain assembly for flexible electronics - Haiyue Miao; Gang Huang; Yiyang Liu; Xiaojuan Huang; Chongyang Zheng; Xi Zhang; Changwu Dong; Xiaobin Fu; Hailong Huang; Min Ge; Hongtao Liu; Yuan Qian (Chemical Engineering Journal, 2025)

Advance and perspective of carbon-based aerogels and their composites - Yanfeng Fu; Hui Ye; Ke Yuan; Qinxin Wang; Longhui Ge; Sheng Cui (Chemical Engineering Journal, 2025)

Distribution patterns and driving forces of soil fungal communities along elevational gradients on two snow mountains in the Hengduan Mountain Range - Shiqi Zhang; Zhenjiao Cao; Wei Fu; Congcong Shen; Zhipeng Hao; Guoxin Sun; Yuan Ge; Limei Zhang; Xin Zhang; Baodong Chen (Soil Ecology Letters, 2025)

Nitrogen deposition reshapes biological nitrogen fixation and soil diazotrophic communities across urban and rural forests - Ruoxian Fu; Dianlong Ge; Jinsheng Li; Yuanchun Yu; Zhuangzhuang Qian; Xiaoniu Xu; Chunhui Li; Biao Zhu; Xiao Tao (CATENA, 2025)

Impact of Different CO2/N2 Mixing Ratios on Anthracite Pore Structure Evolution - Zhaolong Ge; Xinyu Wang; Xinguo Yang; Wenyu Fu; Xinge Zhao; Yunzhong Jia (Natural Resources Research, 2025)

The SnRK1 kinase TaSnRK1.10 positively regulates heavy metal chromium tolerance mainly by mediating reactive oxygen species homeostasis and activating the phenylpropanoid biosynthetic pathway in wheat - Yihan Fu; Cong Chen; Pei Pei; Xiangyang Hao; Jiajia Jin; Shujie Shi; Qiang Ge; Pengfei Wang; Gezi Li; Guozhan Fu; Changqing Du; Guozhang Kang (Journal of Hazardous Materials, 2025)

Tabular prior-data fitted network for urban air temperature inference and high temperature risk assessment - Zhongqi Yu; Ruqing Yu; Xinyi Ge; Jiayan Fu; Yiteng Hu; Shisheng Chen (Sustainable Cities and Society, 2025)

Aqueous production of sulfur-containing aerosols from nitroaromatic compounds and SO2 in wintertime urban haze - Ning Yang; Junfeng Wang; Daniel J. Jacob; Jianhuai Ye; Ming Sheng; Mutong Niu; Yiming Qin; Xinlei Ge; Yele Sun; Zifa Wang; Yuhang Wang; Fengchang Wu; et al. (Science Bulletin, 2025)

Paired electrocatalysis for simultaneous anodic oxidation of tetracycline and cathodic nitrate reduction to ammonia - Chunhong Fu; Huizhong Wu; Jiangli Sun; Ge Song; Minghua Zhou (Journal of Hazardous Materials, 2025)

Semi-quantitative lipidomics reveals the characteristics of lipid metabolism in sheep milk fermentation - Fenfen Tong; Shangchen Fu; Yufei Shen; Xiaowei Hou; Mengjia Liu; Zhi Wang; Xu Zhang; Shuangshuang Wang; Wupeng Ge (Food Research International, 2025)

Inorganic arsenic in aquatic products in Shenzhen, China from 2018 to 2024: Levels, temporal variation and health risk assessment - Bo Fu; Kai Lin; Sisi Yu; Yiming Ge; Xinjie Li; Wenchao Zhu; Lei Tan; Rui Wang; Jixi Ou; Shaoyou Lu (Food and Chemical Toxicology, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Branch segmentation and phenotype extraction of apple trees based on improved Laplace algorithm - Long Li; Wei Fu; Bin Zhang; Yuqi Yang; Yun Ge; Congju Shen (Computers and Electronics in Agriculture, 2025)

The role of ATG7-mediated ferroptosis in formaldehyde-induced ovarian injury in rats - Kun Mao; Hao-zhe Yan; Jia-qi Yang; Zi-xin Yin; Xin-qi Gao; Hao-fu Liu; Heng Su; Yuan-yuan Geng; Pan Ge; Dang-xia Zhou (Reproductive Toxicology, 2025)

A new in situ fracturing-enhanced oxidative remediation for various low-permeability phenanthrene-contaminated soils: Oxidation effectiveness and kinetics of potassium permanganate - Fu-Jiang Shi; Shi-Jin Feng; Jiu-Ge Niu; Qi-Teng Zheng; Xiao-Lei Zhang (Journal of Hazardous Materials, 2025)

Construction of site-specific immobilized lipase in bio-inspired “rigid and flexible” composite PVIm/ZIF-8 for long-cycle biodiesel synthesis from waste cooking oil - Qian Wang; Xinyuan Zheng; Meiling Ge; Rong Chen; Fangpei Ma; Jianming Pan; Fu Yang (Chemical Engineering Journal, 2025)

Remediation effectiveness and mechanism on surfactant-enhanced remediation of low-permeability petroleum hydrocarbon contaminated soil under fracturing conditions - Shi-Jin Feng; Jiu-Ge Niu; Fu-Jiang Shi; Qi-Teng Zheng; Meng-Wen Gao (Journal of Hydrology, 2025)

Soil-aged microplastics exhibit stronger effects than air- and rainwater-aged ones on the network complexity and assembly process of soil microbial community - Faying Fu; Shu Wang; Xinran Zhang; Yu Xia; Hui Deng; Yuanyuan Zhao; Ying Zhang; Chengjun Ge (Journal of Environmental Chemical Engineering, 2025)

Polysaccharide metabolic pattern of Cytophagales and Flavobacteriales: a comprehensive genomics approach - Kuo-Jian Ma; Yong-Lian Ye; Yu-Kang Li; Ge-Yi Fu; Yue-Hong Wu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2025)
The complete metabolism of carbohydrates, as the most abundant and structurally diverse organic matter on earth, requires the involvement of different carbohydrate-active enzymes (CAZymes). Flavobacteriales and Cytophagales are two groups whose members specialize in polysaccharide metabolism, but research on their polysaccharide metabolic patterns based on the overall CAZymes is scarce. In this study, we analyzed 702 filtered genomes of Flavobacteriales and Cytophagales and obtained 100,445 CAZymes. According to their taxonomic status and living environment, we explored the impact of taxonomic status, isolation source, and environmental condition on their potential polysaccharide metabolic patterns. The results indicated significant differences in the CAZyme composition among different taxonomic statuses or environments. Compared with the Flavobacteriales genomes, the genomes of Cytophagales possess more abundant and diverse CAZymes, but have fewer unique CAZyme families. Genomes from different families vary greatly in terms of CAZyme family diversity and composition, but relatively small divergences were found from families in the same order. Furthermore, our findings indicated that genomes from the marine and tidal flat environments share more similarities in CAZyme family composition and diversity compared with the terrestrial genomes. Extreme environments greatly constrain the types of CAZyme families present, and certain CAZyme families are significantly lower than those in normal environments. Although significant differences were found among genomes from both different taxonomic statuses and environments, the dimensionality reduction and the clustering analysis based on CAZyme composition indicated that evolutionary status is the main factor influencing the polysaccharide metabolic patterns of these strains. The correlations among CAZyme families indicated that the majority of these families are synergistically involved in polysaccharide metabolism. This study provides a comprehensive profile of the CAZymes in Flavobacteriales and Cytophagales, highlighting the role of evolutionary status in shaping the polysaccharide metabolic patterns and the prevalence of synergism among CAZyme families. These findings have implications for understanding microbial carbohydrate metabolism in different environments.

Dynamic responses and adsorption mechanisms of Chlamydomonas reinhardtii extracellular polymeric substances under Cd, Cu, Pb, and Zn exposure - Chonghua Li; Peihuan Li; Hongxuan Fu; Zijian She; Chunhua Zhang; Yichun Li; Mu Zhang; Ying Ge (Environmental Pollution, 2025)

A flexible, antifreezing, and long-term stable cellulose ionic conductive hydrogel via one-step preparation for flexible electronic sensors - Haiyue Miao; Yiyang Liu; Chongyang Zheng; Xiaojuan Huang; Yidan Song; Lulu Tong; Changwu Dong; Xiaobin Fu; Hailong Huang; Min Ge; Hongtao Liu; Yuan Qian (Carbohydrate Polymers, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Catalytic degradation of ethyl acetate at room temperature over Ni/NAC monolithic catalyst - Xiangci Wu; Chenglong Dai; Lisheng Zhang; Ge Gao; Jiahui Shi; Dan Zhao; Bingfeng Fu; Shejiang Liu; Jianfeng Fu; Hui Ding (Journal of Environmental Chemical Engineering, 2025)

An improved method to accelerate the acquisition efficiency of the T1-T2 spectrum based on the IR-BSSFP-CPMG pulse sequence∗ - Fu Zuo; Xinmin Ge; Lanchang Xing; Bohan Wu; Yiren Fan; Jackson Jervis Junior; Bin Wang (Computers & Geosciences, 2025)

Highly flexible and enhanced catalytic oxidation of Fe-doped Co3O4/SiOC core-shell heterostructured fibrous membranes for flow-through removal of organic contaminants - Haoru Shan; Wenqiang Wang; Zhirong Wang; Mengjiao Zhang; Yuxin Ma; Wenzhe Li; Qixia Liu; Xinglei Zhao; Jianlong Ge; Qiuxia Fu (Chemical Engineering Journal, 2025)

Electrically responsive photonic crystals with highly sensitive response and low power consumption for color displays - Qianqian Fu; Yanxuan Zhao; Wenyuan Yu; Jianping Ge (Chemical Engineering Journal, 2025)

Tectono-sequence evolution of an extensional strike-slip composite basin, a case study of the Miaoxi'nan sub-sag in the eastern Bohai Bay Basin - Sheng Fu; Haifeng Yang; Lijun Song; Wei Zhou; Jiawang Ge; Yanqin Guo (Marine and Petroleum Geology, 2025)

Characteristics and Functions of Rhizosphere Bacterial Communities of Camelli sinensis cv. Shifocui with Cold Resistance Characteristics in Anhui Province, China - Shuiqin Shi; Enhui He; Junjie Ma; Mengrui Ge; Jiahui Gao; Tianyi Peng; Yu Fu; Jianfen Wang; Li Gong; Duoqi Zhou; Yafang Liu (Current Microbiology, 2025)

Modeling and control of dissolved oxygen in recirculating aquaculture systems: A circadian rhythm analysis approach and GSMPC controller - Fu Chai; Quanwu Ge; Yihan Yin; Daoliang Li; Yang Wang (Computers and Electronics in Agriculture, 2024)

Impact of microplastics on plant physiology: A meta-analysis of dose, particle size, and crop type interactions in agricultural ecosystems - Xinwei Shi; Ruiying Shi; Xiuping Fu; Yuexing Zhao; Yichen Ge; Jinzheng Liu; Cuihong Chen; Weitao Liu (Science of The Total Environment, 2024)

Deciphering how endogenous mangrove litterfall influences organic matters transformation driven by microbes in sediment with exogenous microplastics inputs - Yu Xia; Shu Wang; Xinran Zhang; Faying Fu; Hui Deng; Yuanyuan Zhao; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2024)

Semiflexible spiro-branched membrane with adjustable sub-nanoscale channels and high positive charge for acid recovery - Huaqing Zhang; Mingyue Wu; Liang Wu; Rongqiang Fu; Zhaoming Liu; Xiaolin Ge; Tongwen Xu (Chemical Engineering Journal, 2024)

Individual traits modify environmental effects on interaction, connectivity, and productivity of macrophyte community - Hui Fu; Jingjing Guo; Xianjun He; Yaoqi Chen; Zhouhang Wu; Yili Ge; Guojun Cai (Hydrobiologia, 2024)

Short-term sedimentary evidence for increasing diatoms in Arctic fjords in a warming world - Fu-Tao Fang; Zhuo-Yi Zhu; Fred Wenger; Jian-Zhong Ge; Jin-Zhou Du; Bing Deng; Hong-Mei Ma; Rui-Feng Zhang; Yu Zhang (Science of The Total Environment, 2024)

Trace elements in PM2.5 from 2016 to 2021 in Shenzhen, China: Concentrations, temporal and spatial distribution, and related human inhalation exposure risk - Jialei Yang; Xin Chen; Xiaoheng Li; Jinfeng Fu; Yiming Ge; Zhihui Guo; Jiajia Ji; Shaoyou Lu (Science of The Total Environment, 2024)

The displacement behaviors of CH4-containing anthracite under various injection pressures: The critical role of mineral dissolution and precipitation - Wenyu Fu; Yunzhong Jia; Zhaolong Ge; Chenqing Shang; Xinge Zhao (Gas Science and Engineering, 2024)

Characterization of a short-term processing technology of black garlic with low 5-HMF content - Jun Liu; Jing Li; Shihao Ge; Xiaoyu Fu; Jiamin Zhu; Mengnan Wang; Yanrong Wang; Xiaoxiao Huang; Xinzheng Qin; Yixian Tu; Jun Xing; Chao Ma; et al. (Food Control, 2024)

Parabens, bisphenols, and triclosan in coral polyps, algae, and sediments from sanya, China: Occurrence, profiles, and environmental implications - Yiming Ge; Han Zhang; Jinfeng Fu; Zhihui Guo; Qiulu Dong; Jiaxin Yu; Zhiling Mo; Yuxi Lai; Jialei Yang; Shaoyou Lu (Environmental Pollution, 2024)

Green massive mechanical synthesis of highly efficient Zn-Doped Cs3Cu2I5 for LED and X-ray imaging applications - Qi-Hua Yang; Gui-Hua Li; Yu-Chen Ao; Shu-Juan Zhao; Han-Qi Wei; Le Fu; Zhi-Wei Luo; Tian-Liang Zhou; Chu-Jie Wang; Ge-Mei Cai (Chemical Engineering Journal, 2024)

Cascading effects of human activities and ENSO on the water quality of Poyang Lake in China - Yili Ge; Zhouhang Wu; Yaoqi Chen; Peiqin Guo; Aiping Wu; Huanyao Liu; Guixiang Yuan; Youzhi Li; Hui Fu; Erik Jeppesen (CATENA, 2024)

Corrigendum to ``Temporal shifts in the phytoplankton network in a large eutrophic shallow freshwater lake subjected to major environmental changes due to human interventions'' [Water Research 261 (2024) 122054] - Guojun Cai; Yili Ge; Zheng Dong; Yu Liao; Yaoqi Chen; Aiping Wu; Youzhi Li; Huanyao Liu; Guixiang Yuan; Jianming Deng; Hui Fu; Erik Jeppesen (Water Research, 2024)

Synergistic strategy via modulated energy filtering and hierarchical defects evolution for high performance GeTe thermoelectrics - Ge Fu; Shangchao Lin; Yixuan Liu; Jie Xiao; Changying Zhao (Chemical Engineering Journal, 2024)

Etiological study on forest fire accidents using Bow-tie model and Bayesian network - Shi-yi Li; Xin Li; Fu-qiang Yang; Fan-liang Ge (Natural Hazards, 2024)

Temporal shifts in the phytoplankton network in a large eutrophic shallow freshwater lake subjected to major environmental changes due to human interventions - Guojun Cai; Yili Ge; Zheng Dong; Yu Liao; Yaoqi Chen; Aiping Wu; Youzhi Li; Huanyao Liu; Guixiang Yuan; Jianming Deng; Hui Fu; Erik Jeppesen (Water Research, 2024)

Enhanced Fenton-like catalysis via interfacial regulation of g-C3N4 for efficient aromatic organic pollutant degradation - Bin Zhou; Qingsong Liu; Caihong Zheng; Yao Ge; Lili Huang; Haoyang Fu; Shengqiong Fang (Environmental Pollution, 2024)

Iodine/soluble starch cryogel: An iodine-based antiseptic with instant water-solubility, improved stability, and potent bactericidal activity - Wei Sun; Zi-Xi Wang; Yuxin Guo; Chengcheng Li; Ge Gao; Fu-Gen Wu (Carbohydrate Polymers, 2024)

Undervalued dry riverbeds: A key factor in equating intermittent river CO2 emissions to perennial rivers - Chao Qin; Yuan Xue; Mengzhen Xu; Lishan Ran; Dongfeng Li; Ge Wang; Defan Cun; Baosheng Wu; Xudong Fu; Guangqian Wang (Water Research, 2024)

Cation-permselective membranes enabled by synergistic ion channels of crown ethers and anionic sites - Yanran Zhu; Bin Wu; Qian Chen; Guanyin Gao; Xingya Li; Chenxiao Jiang; Rongqiang Fu; Zhaoming Liu; Liang Ge; Tongwen Xu (Chemical Engineering Journal, 2024)

Aβ-Aggregation-Generated Blue Autofluorescence Illuminates Senile Plaques as well as Complex Blood and Vascular Pathologies in Alzheimer’s Disease - Hualin Fu; Jilong Li; Chunlei Zhang; Peng Du; Guo Gao; Qiqi Ge; Xinping Guan; Daxiang Cui (Neuroscience Bulletin, 2024)

m6A-Mediated Upregulation of lncRNA CHASERR Promotes the Progression of Glioma by Modulating the miR-6893-3p/TRIM14 Axis - Xingwei Wu; Minjie Fu; Chang Ge; Hanyu Zhou; Haoyu Huang; Min Zhong; Mengying Zhang; Hao Xu; Guoping Zhu; Wei Hua; Kun Lv; Hui Yang (Molecular Neurobiology, 2024)

Colorimetric aptasensor utilizing MOF-235 with exceptional peroxidase-like activity for the detection of oxytetracycline residues in raw milk - Long Wang; Xia Lu; Yan Zhang; Yuxin Wang; Yi Ding; Mengjia Liu; Shangchen Fu; Wupeng Ge (Food Chemistry, 2024)

Unveiling toxicity profile for food risk components: A manually curated toxicological databank of food-relevant chemicals - Xing-Xing Shi; Fan Wang; Zhi-Zheng Wang; Guang-Yi Huang; Min Li; Jesus Simal-Gandara; Ge-Fei Hao; Guang-Fu Yang (Critical Reviews in Food Science and Nutrition, 2024)

SLC11A1 promotes kidney renal clear cell carcinoma (KIRC) progression by remodeling the tumor microenvironment - Ding Wu; Yulin Zhou; Xiuquan Shi; Xiaoming Yi; Zhengcheng Sheng; Li Fan; Jingping Ge; Wen Cheng; Wenquan Zhou; Haowei He; Dian Fu (Toxicology and Applied Pharmacology, 2024)

Ratiometric fluorescence platform for the ultrasensitive detection of kanamycin based on split aptamer co-recognition triggers Mg2+-DNAzyme-driven DNA walker systems - Xia Lu; Long Wang; Guowei Li; Yuxin Wang; Guo Hao; Yi Ding; Mengjia Liu; Shangchen Fu; Liqing Xu; Na Ge; Wupeng Ge (Science of The Total Environment, 2024)

Exposure to the environmental pollutant chlorpyrifos induces hepatic toxicity through activation of the JAK/STAT and MAPK pathways - Huiyang Fu; Yao Ge; Xiyuan Liu; Siwei Deng; Jun Li; Peng Tan; Ying Yang; Zhenlong Wu (Science of The Total Environment, 2024)

Integrating untargeted and pseudotargeted metabolomics and network analysis reveals the interventional effects of red yeast rice on rat serum metabolites - Ge Xun; Yingxuan Li; Yifan Zhang; Song Li; Yanhua Gao; Yujuan Chen; Ding Zhang; Hongyang Ni; Fangfang Liu; Yan Fu; Xu Wang; Qiao Wang (Food Bioscience, 2024)

Delaying crystallization and anchoring the grain boundaries defects via π-π stacked molecules for efficient and stable wide-bandgap perovskite solar cells - Jinliang Shen; Na Li; Yuhang Wang; Xiang Ge; Junlei Tao; Song Yin; Xingkun Ning; Tingwei He; Guangsheng Fu; Shaopeng Yang (Chemical Engineering Journal, 2024)

Developmental pleiotropy of SDP1 from seedling to mature stages in B. napus - Baolong Tao; Yina Ma; Liqin Wang; Chao He; Junlin Chen; Xiaoyu Ge; Lun Zhao; Jing Wen; Bin Yi; Jinxing Tu; Tingdong Fu; Jinxiong Shen (Plant Molecular Biology, 2024)

Identification of important gene signatures in schizophrenia through feature fusion and genetic algorithm - Zhixiong Chen; Ruiquan Ge; Changmiao Wang; Ahmed Elazab; Xianjun Fu; Wenwen Min; Feiwei Qin; Gangyong Jia; Xiaopeng Fan (Mammalian Genome, 2024)

Nitrogen fertilization enhances growth and development of Cacopsylla chinensis by modifying production of ferulic acid and amino acids in pears - Zifang Qin; Yang Ge; Wantong Jia; Liu Zhang; Mingyue Feng; Xinzheng Huang; Zhen Fu; Wangpeng Shi (Journal of Pest Science, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Draconibacterium aestuarii sp.nov., a Glycolipid-Producing Bacterium Isolated from Tidal Flat Sediment and Emended Description of the Genus Draconibacterium - Jia-Yan Wang; Sha-Sha Qiu; Yue Su; Wei-Yu Pan; Tao Wang; Wen-Wu Zhang; Ge-Yi Fu; Min Wu (Current Microbiology, 2024)

A method for tight gas reservoir evaluation based on nuclear logging - Xinyue Fu; Wensheng Wu; Bowen Sun; Mingsong Wu; Hu Wang; Yunlong Ge (Acta Geophysica, 2024)

Effects of inter-basin transfers on watershed hydrology and vegetation greening in a large inland river basin - Lin Wang; Wei Wei; Ge Sun; Bojie Fu; Liding Chen; Xiaoming Feng; Philippe Ciais; Bhaskar Mitra; Lixin Wang (Journal of Hydrology, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Green manure substitution for potassium fertilizer promotes agro-ecosystem multifunctionality via triggering interactions among soil, plant and rhizosphere microbiome - Qing Zeng; Mei Yin; Li-Bo Fu; Brajesh K. Singh; Si-Yi Liu; Hua Chen; An-Hui Ge; Li-Li Han; Li-Mei Zhang (Plant and Soil, 2024)

Semi-automatic identification of rock discontinuity orientation based on 3D point clouds and its engineering application - Jingyu Kang; Xiaodong Fu; Qian Sheng; Yunfeng Ge; Jian Chen; Haibin Wang (Bulletin of Engineering Geology and the Environment, 2024)

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

Synergy of Mo doping and heterostructures in FeCo2S4@Mo-NiCo LDH/NF as durable and corrosion-resistance bifunctional electrocatalyst towards seawater electrolysis at industrial current density - Suyu Ge; Xueran Shen; Jiaxin Gao; Kaixuan Ma; Haoyu Zhao; Ruru Fu; Caihong Feng; Yun Zhao; Qingze Jiao; Hansheng Li (Chemical Engineering Journal, 2024)

Towards standardizing automated image analysis with artificial intelligence for biodiversity - Peng Zhou; Yu-Xin Bu; Ge-Yi Fu; Chun-Sheng Wang; Xue-Wei Xu; Xiaoyong Pan (Frontiers in Marine Science, 2024)

Preparation of lanthanum-modified bentonite and its combination with oxidant and coagulant for phosphorus and algae removal - Ge Han; Shenshen Cui; Zheng Fu; Xinshan Song; Xiaohua Chen; Yuhui Wang (Journal of Water Process Engineering, 2024)

Importance of forest stand structures for gross rainfall partitioning on China’s Loess Plateau - Xu Hu; Zhaoqi Fu; Ge Sun; Biao Wang; Keyan Liu; Churui Zhang; Lu Han; Lixin Chen; Zhiqiang Zhang (Journal of Hydrology, 2024)

Soil total and available C:N:P stoichiometry among different parent material soil profiles in rubber plantations of Hainan Island, China - Yuzhu Li; Yue Zhao; Xuelian Bao; Hongtu Xie; Xiaotao Lü; Yangang Fu; Shixin Tang; Chengjun Ge; Chao Liang (Geoderma Regional, 2024)

Automatic detection tree crown and height using Mask R-CNN based on unmanned aerial vehicles images for biomass mapping - Hancong Fu; Hengqian Zhao; Jinbao Jiang; Yujiao Zhang; Ge Liu; Wanshan Xiao; Shouhang Du; Wei Guo; Xuanqi Liu (Forest Ecology and Management, 2024)

Flutter control optimization for a 5000 m suspension bridge with active aerodynamic flaps: a CFD-enabled strategy - Zilong Wang; Lin Zhao; Yiheng Fu; Genshen Fang; Wei Cui; Ke Li; Yaojun Ge (Engineering Structures, 2024)

Uncovering Se, P co-doping effect in MnO2 toward high-performance aqueous zinc-ion batteries - Kaixuan Ma; Suyu Ge; Ruru Fu; Caihong Feng; Haoyu Zhao; Xueran Shen; Guangfeng Liang; Yun Zhao; Qingze Jiao (Chemical Engineering Journal, 2024)

Inflammation and Brain Structure in Alzheimer’s Disease and Other Neurodegenerative Disorders: a Mendelian Randomization Study - Wei-Shi Liu; Ya-Ru Zhang; Yi-Jun Ge; Hui-Fu Wang; Wei Cheng; Jin-Tai Yu (Molecular Neurobiology, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Seasonal variation and dissolved organic matter influence on the distribution, transformation, and environmental risk of pharmaceuticals and personal care products in coastal zone: A case study of Tianjin, China - Wenrui Yao; Yulin Qi; Yufu Han; Jinfeng Ge; Yuanyuan Dong; Jianwen Wang; Yuanbi Yi; Dietrich A. Volmer; Si-Liang Li; Pingqing Fu (Water Research, 2024)

Weakened casual feedback loops following intensive restoration efforts and climate changes in a large shallow freshwater lake - Hui Fu; Yili Ge; Guojun Cai; Jianmin Deng; Huanyao Liu; Aiping Wu; Youzhi Li; Wei Li; Guixiang Yuan; Erik Jeppesen (Science of The Total Environment, 2024)

Integrated transcriptomic, proteomic, and metabolomic approaches reveal the antifungal mechanism of methyl ferulate against Alternaria alternate - Hui Kong; Shuai Ge; Xia Chang; Saiqing Xu; Haishan Xu; Xincheng Fu; Rongrong Wang; Zisheng Luo; Yang Shan; Shenghua Ding (Postharvest Biology and Technology, 2024)

Self-assembly kieselguhr-based ZSM-5 for catalytic pyrolysis of mask waste to produce high value-added aromatics - Yufei Gu; Hucheng Ge; Yuke Liu; Qi Wei; Tianhua Gao; Hengshuo Gu; Hongbing Fu; Fuwei Li; Hongfei Lin; Lei Miao; Zhixia Li (Fuel, 2024)

Calcium ions induced ι-carrageenan-based gel-coating deposited on zein nanoparticles for encapsulating the curcumin - Qingyuan Ge; Shuang Rong; Chenxi Yin; David Julian McClements; Qi Fu; Qi Li; Yahong Han; Fuguo Liu; Suqing Wang; Shuai Chen (Food Chemistry, 2024)

Spatialized importance of key factors affecting park cooling intensity based on the park scale - Zhihua Liu; Lizhao Fu; Chaofan Wu; Zhenzhen Zhang; Zhaoyang Zhang; Xingwen Lin; Xuan Li; Yuhong Hu; Haixian Ge (Sustainable Cities and Society, 2023)

Prime editing: current advances and therapeutic opportunities in human diseases - Yidian Fu; Xiaoyu He; Xin D. Gao; Fang Li; Shengfang Ge; Zhi Yang; Xianqun Fan (Science Bulletin, 2023)

Plant and animal positive-sense single-stranded RNA viruses encode small proteins important for viral infection in their negative-sense strand - Pan Gong; Qingtang Shen; Mingzhen Zhang; Rui Qiao; Jing Jiang; Lili Su; Siwen Zhao; Shuai Fu; Yu Ma; Linhao Ge; Yaqin Wang; Rosa Lozano-Durán; et al. (Molecular Plant, 2023)

Geomorphologic evidences and hydrologic reconstruction of Holocene catastrophic flood events in the Yarlung Tsangpo Grand Canyon, Eastern Himalaya - Yongqiang Guo; Yonggang Ge; Peini Mao; Tao Liu; Xudong Fu; Shuaihu Wu (Journal of Hydrology, 2023)

Prussian blue analogues-derived zero valent iron to efficiently activate peroxymonosulfate for phenol degradation triggered via reactive oxygen species and high-valent iron-oxo complexes - Tong Wei; Xin-Sheng Zhu; Qi-Xue Wang; Ke-Ke Xu; Fu-Kai Tang; Ming-Zhu Zhang; Shi-Wen Lv; Feng Ge (Environmental Research, 2023)

Multi-omics analysis reveals the mechanism of calcium-reduced quality deterioration in mechanically injured green pepper fruit - Lili Ma; Yanyan Zheng; Zhaoze Sang; Yonghong Ge; Chunmei Bai; Anzhen Fu; Qing Wang; Christopher B. Watkins; Jinhua Zuo (Postharvest Biology and Technology, 2023)

Portable instrument based on color sensor chip for on-site rapid detection of dissolved sulfides in environmental water samples - Ge Gao; Ji Qi; Longwen Fu; Rongfang Zhao; Zhiyang Zhang; Lingxin Chen (Journal of Hazardous Materials, 2023)

Role of garbage classification in air pollution improvement of a municipal solid waste disposal base - Song Gao; Lingning Meng; Xiang Ge; Yuewu Li; Yong Yang; Yusen Duan; Qingyan Fu; Shuwei Zhang; Xuechun Yang; Weiliang Fei; Zheng Jiao (Journal of Cleaner Production, 2023)

Refractory black carbon aerosols in rainwater in the summer of 2019 in Beijing: Mass concentration, size distribution and wet scavenging ratio - Shandong Lei; Baozhu Ge; Hang Liu; Jiannong Quan; Danhui Xu; Yuting Zhang; Weijie Yao; Lu Lei; Yu Tian; Qi Liao; Xiaoyong Liu; Jie Li; et al. (Journal of Environmental Sciences, 2023)

Sequential fermentation with indigenous non-Saccharomyces yeasts and Saccharomyces cerevisiae for flavor and quality enhancement of Longyan dry white wine - Xiaodi Wang; Jiawei Chen; Xiaoxin Ge; Xiaofang Fu; Chao Dang; Jie Wang; Yaqiong Liu (Food Bioscience, 2023)

Semiconductors modified gourd-shaped hollow PtNi and their directional electron and mass transfer effects - Fu-Fei Pu; Yu-Xuan Xiao; Xiong Yang; Fei Yu; Lei Xia; Jiang-Bo Chen; Lu Wu; Jing-Jing Xie; Wen-Ying Zhao; Yu Liu; Li-Ying Wang; Jie Ying; et al. (Chemical Engineering Journal, 2023)

The heterogeneity of microbial diversity and its drivers in two types of sediments from tidal flats in Beibu Gulf, China - Yong-Lian Ye; Kuo-Jian Ma; Yun-Han Fu; Zhi-Cheng Wu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Mudflats and sandflats are two common types of coastal tidal flats, the structure and function differences of microbial communities between them are still underappreciated. Beibu Gulf is a diurnal tidal regime located in China, the differences between the two type of tidal flats could be more distinct. In this study, we collected a total of 6 samples from Beibu Gulf, consisting of 3 sandflats samples and 3 mudflats samples, classified based on clay and silt content. Generally, the mudflats samples exhibited higher levels of NH 4 + _N and TOC, but lower in ORP and pH. The microbial diversity of the two types of tidal flats was investigated, revealing great differences existed and sandflats had higher microbial richness and diversity than mudflats. Furthermore, we analyzed the association between microbial communities and environmental factors, finding NH 4 + _N to have the highest contribution to the total variation in microbial community structure, and microbial groups such as Desulfobacterota, Campilobacterota, Chloroflexota, Calditrichota, Spirochaetota, Zixibacteria, Latescibacterota and Sva0485 group in mudflats were positively associated with NH 4 + _N. The functions of microbial community were predicted using metagenomic sequences and metagenome assembled genome (MAG). Mudflats contained more genes for carbon fixation. Nitrate and nitrite reduction were widely existed in mudflats and sandflats, but nitrogen fixation was only existed in mudflats, and Campilobacterota , Desulfobacterota and Gammaproteobacteria MAGs were mainly responsible for it. Sandflats composed more genes for ammonium oxidation, but no MAG was found whether in sandflats or mudflats. Microbes in mudflats exhibited a greater abundance of genes related to sulfur cycling, especially in reduction process, unique MAGs in mudflats such as Calditrichota, Chloroflexota, Desulfobacterota and Zixibacteria MAGs are responsible for sulfate and sulfite reduction. Finally, we predicted functions of ammonium related microbes in mudflats based on MAGs and found Campilobacterota and Desulfobacterota MAGs were important for high accumulation of ammonium in mudflats. This study illuminated the structural and functional differences of microbial communities in mudflats and sandflats, providing new insights into the relationship of microbial communities and environment in the tidal flat.

Spatial distribution of heavy metal contaminants: The effects of water-sediment regulation in the Henan section of the Yellow River - Songtao Liu; Furong Yu; Tao Lang; Yuekun Ji; Yu Fu; Jianuo Zhang; Chang Ge (Science of The Total Environment, 2023)

Concatenating wide-parallax satellite orthoimages for simplified regional mapping via utilizing line-point consistency - Ziming Tu; Xiubin Yang; Zongqiang Fu; Suining Gao; Ge Yang; Li Jiang; Mo Wu; Shaoen Wang (International Journal of Remote Sensing, 2023)

Metagenome-based analysis of carbon-fixing microorganisms and their carbon-fixing pathways in deep-sea sediments of the southwestern Indian Ocean - Xiao-Lan Yue; Lin Xu; Li Cui; Ge-Yi Fu; Xue-Wei Xu (Marine Genomics, 2023)

Hepatotoxicity screening and ranking of structurally different pyrrolizidine alkaloids in zebrafish - Yueyang Pan; Jiang Ma; Hui Zhao; Peter P. Fu; Ge Lin (Food and Chemical Toxicology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Genomic and phylotypic properties of three novel marine Bacteroidota from bare tidal flats reveal insights into their potential of polysaccharide metabolism - Kuo-Jian Ma; Yong-Lian Ye; Yun-Han Fu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Special geographical location and abundant organic matter profiles in tidal flats have resulted in great microbial diversity, in which Bacteroidota strains are considered as one of the primary degraders of polysaccharides, playing a crucial role in the carbon cycle. In this study, we collected sediment or sand samples from 34 bare tidal flats in China and investigated the profile of culturable bacteria, selected three Bacteroidota for polyphasic taxonomic analysis and revealed their polysaccharide metabolic potential. Totally, we isolated 352 pure cultured bacteria and they mainly distributed in Bacteroidota , Pseudomonadota , Bacillota , and Actinomycetota . It is shown that the bare tidal flats contained a large number of potential novel species, mainly distributed in Flavobacteriales and Cytophagales within Bacteroidota . Three Bacteroidota strains, M17 T , M82 T , and M415 T , isolated from mudflat were selected for polyphasic taxonomic analysis. The 16S rRNA gene sequence similarity between strain M17 T and Mangrovivirga cuniculi KCTC 72349 T was 99.28%, and less than 90.09% with other species; strain M82 T shared the highest 16S rRNA gene sequence similarity of 97.85% with Pontibacter litorisediminis KCTC 52252 T , and less than 97.43% with other species; strain M415T had higher 16S rRNA gene sequence similarities with type species of genera Eudoraea (92.62-93.68%), Zeaxanthinibacter (92.02-92.91%), and Muriicola (92.21-92.83%). Phylogenetic analysis based on 16S rRNA gene sequences and single-copy orthologous clusters showed that strains M17 T and M82 T represent novel species within the genus Mangrovivirga and Pontibacter , respectively, and strain M415 T represents a novel species of a novel genus within the family Flavobacteriaceae . The potential in polysaccharide metabolism of all these three strains was analyzed by genomes. The analysis revealed that glycoside hydrolases and glycosyltransferases account for more than 70% of the total CAZymes. Additionally, the numbers of polysaccharide utilization loci (PULs) and annotated CAZymes in Cytophagales spp. M17 T and M82 T were found to be higher than those in Flavobacteriales sp. M415 T . Highly specialized saccharolytic systems and the presence of numerous diversified CAZymes for obtaining energy through polysaccharide metabolism were speculated to help the three novel strains adapt to the utilization of both terrestrial and marine polysaccharides.

Carbonaceous nanofibrous membranes with enhanced superhydrophilicity and underwater superoleophobicity for effective purification of emulsified oily wastewater - Hong Chen; Anqi Zhou; Yifan Zhang; Xueqin Wang; Gangwei Pan; Sijun Xu; Qixia Liu; Haoru Shan; Qiuxia Fu; Jianlong Ge (Chemical Engineering Journal, 2023)

A review of filamentous sludge bulking controls from conventional methods to emerging quorum quenching strategies - Xin Lu; Ge Yan; Liang Fu; Bin Cui; Jinfeng Wang; Dandan Zhou (Water Research, 2023)

General synthesis of flexible CuO nanoparticles-anchored ZrO2 nanofibrous membranes for catalytic oxidation of tetracycline - Haoru Shan; Wenqiang Wang; Zhirong Wang; Jianlong Ge; Qixia Liu; Wei Zhang; Qiuxia Fu (Chemical Engineering Journal, 2023)

Engineered urinary-derived extracellular vesicles loaded nanoenzymes as Trojan horses to regulate the inflammatory microenvironment for treatment of Alzheimer's disease - Zetai Bai; Kezhen Ge; Jingjing Fu; Dehong Yu; Zhiyuan Hua; Senlin Xue; Zheng Li; Weiwei Sheng; Xiunan Wu; Fenfang Gao; Deqin Geng; Fenglei Gao (Chemical Engineering Journal, 2023)

Dunaliella Ds-26-16 acts as a global regulator to enhance salt tolerance by coordinating multiple responses in Arabidopsis seedlings - Si-Yue Liu; Jin-Ge Xie; Xi-Wen Chen; De-Fu Chen (Planta, 2023)

Deletion of the cheZ gene results in the loss of swimming ability and the decrease of adhesion ability to Caco-2 cells in Escherichia coli Nissle 1917 - Bingming Ou; Haihui Lv; Hua Ge; Dexiang Fu; Xin Lin; Saiqiao Huang; Xiaojie Chen; Yufu Liu; Sainan Li; Wenhua Liu; Lihua Huang; Ying Yang; et al. (Folia Microbiologica, 2023)

Causes of the discordance in the south-north distribution of the 2017 Jiuzhaigou earthquake sequences - Zhi-Tong Jin; Jia-Lu Liu; Yong-Ge Wan; Shu-Zhong Sheng; Fu-Chang Wang; Xiao-Tao Zhang; Gan Feng (Applied Geophysics, 2023)

A comparative study of the accumulation and detoxification of copper and zinc in Chlamydomonas reinhardtii: The role of extracellular polymeric substances - Chonghua Li; Peihuan Li; Hongxuan Fu; Jiale Chen; Menglei Ye; Suhua Zhai; Fan Hu; Chunhua Zhang; Ying Ge; Claude Fortin (Science of The Total Environment, 2023)

Transcriptomics and gas chromatography-mass spectrometry metabolomics reveal the mechanism of heat shock combined with 1-methylcyclopropene to regulate the cuticle wax of jujube fruit during storage - Shuai Ge; Rongrong Wang; Lvzhu Yang; Hui Kong; Xia Chang; Xincheng Fu; Yang Shan; Shenghua Ding (Food Chemistry, 2023)

Experimental investigation of the seismic performance of precast post-tensioned segmental bridge piers with stainless energy-dissipating bars - Jian-Yu Fu; Xiao Ge; Jian-Tao Li; Zhi-Guo Sun; Hui Qian; Dong-Sheng Wang (Engineering Structures, 2023)

Ion transmembrane behaviors in selective electrodialysis for acid recovery: Impact of ion categories - Junying Yan; Huangying Wang; Haiyang Yan; Ruirui Li; Rong Fu; Weicheng Fu; Liang Ge; Baoying Wang; Yaoming Wang; Tongwen Xu (Desalination, 2023)

Functional groups and seasonal diversity of crustacean zooplankton in adjacent waters of Haizhou Bay, South Yellow Sea - Zeqi Zheng; Shunan Fu; Yixuan Li; Ruping Ge; Hongju Chen; Zhenjiang Ye; Yunyun Zhuang; Guangxing Liu (Journal of Oceanology and Limnology, 2023)

EchoAI: A deep-learning based model for classification of echinoderms in global oceans - Zhinuo Zhou; Ge-Yi Fu; Yi Fang; Ye Yuan; Hong-Bin Shen; Chun-Sheng Wang; Xue-Wei Xu; Peng Zhou; Xiaoyong Pan (Frontiers in Marine Science, 2023)
Introduction In response to the need for automated classification in global marine biological studies, deep learning is applied to image-based classification of marine echinoderms. Methods Images of marine echinoderms are collected and classified according to their systematic taxonomy. The images belong to 5 classes, 38 orders, 145 families, 459 genera, and 1021 species, respectively. The deep learning model, EfficientNetV2, outperforms the competing model and is chosen for developing the automated classification tool, EchoAI. Then, the EfficientNetV2-based tool, EchoAI is applied to each taxonomic level. Results The accuracy for the test dataset was 0.980 (class), 0.876 (order), 0.738 (family), 0.612 (genus), and 0.469 (species), respectively. Online prediction service is provided. Discussion The EchoAI model and results are facilitated for investigating the diversity, abundance and distribution of species at the global scale, and the methodological strategy can also be applied to image classification of other categories of marine organisms, which is of great significance for global marine studies. EchoAI is freely available at http://www.csbio.sjtu.edu.cn/bioinf/EchoAI/ for academic use.

Sulfur dioxide may predominate in the adverse effects of ambient air pollutants on semen quality among the general population in Hefei, China - Feng Zhang; Hang Li; Wenting Xu; Ge Song; Zhanpeng Wang; Xiaohong Mao; Yiqiu Wei; Mengyang Dai; Yuying Zhang; Qunshan Shen; Feifei Fu; Jing Tan; et al. (Science of The Total Environment, 2023)

Chitosan oligosaccharide alleviates and removes the toxicological effects of organophosphorus pesticide chlorpyrifos residues - Huiyang Fu; Haozhen Liu; Yao Ge; Yinfeng Chen; Peng Tan; Jun Bai; Zhaolai Dai; Ying Yang; Zhenlong Wu (Journal of Hazardous Materials, 2023)

Mangrove degradation retarded microplastics weathering and affected metabolic activities of microplastics-associated microbes - Hui Deng; Yuqing Zhang; Dazhen Li; Qianqian Fu; Jianxiong He; Yuanyuan Zhao; Dan Feng; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2023)

24-Epibrassinolide Enhances Resistance Against Colletotrichum fructicola by Promoting Lignin Biosynthesis in Camellia sinensis L. - Lan Zhang; Zheng Zhang; Golam Jalal Ahammed; Xiaorong Wang; Huihan Fang; Peng Yan; Li-Ping Zhang; Shibei Ge; Jianyu Fu; Wen-Yan Han; Xin Li (Journal of Plant Growth Regulation, 2023)

Decoupling of N and P aggravated upward along food chains in an urban river ecosystem - Shenqun An; Zhengbing Yan; Ying Song; Qiang Fu; Feiyang Ge; Zehao Wu; Wei An; Wenxuan Han (Chemosphere, 2023)

Surprising leopard restoration in fragmented ecosystems reveals connections as the secret to conservation success - Fu Yanwen; Zhao Guojing; Dai Wenqian; Wang Yue; Li Jiawei; Tan Mengyu; Li Yan; Liu Haoran; Xie Bing; Jin Xiao; Fan Enyu; Zhao Lulu; et al. (Science of The Total Environment, 2023)

Reclaimed water use improved polluted water's self-purification capacity --Evidenced by water quality factors and bacterial community structure - Shenqun An; Ying Song; Qiang Fu; Rong Qi; Zehao Wu; Feiyang Ge; Xiaoqian Lu; Wei An; Wenxuan Han (Journal of Cleaner Production, 2023)

Impact of flow velocity on the heterogeneous reaction of SO2 over Fe2O3 - Yangyang Liu; Tao Wang; Qiuyue Ge; Zhuocheng Shi; Kejian Li; Kedong Gong; Lifang Xie; Wei Wang; Qianlong Wang; Jin Han; Hongbo Fu; Jianmin Chen; et al. (Atmospheric Environment, 2023)

Necroptosis-related subtypes are associated with bronchiectasis in pulmonary non-tuberculous mycobacteria-infected patients: a perspective based on transcriptomic analysis - Hao Qian; Ai Ge; Ji-Jin Jiang; Jin-Fu Xu (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

The distinct resistance mechanisms of cyanobacteria and green algae to sulfamethoxazole and its implications for environmental risk assessment - Yibo Zhang; Ming Li; Fang Chang; Malan Yi; Hongmei Ge; Jie Fu; Chenyuan Dang (Science of The Total Environment, 2023)

One-step synthesis of porous Li4SiO4 pellets by polyvinyl alcohol (PVA) method for CO2 capture - Ruicheng Fu; Ge Yu; Junna Cheng; Yingchao Hu; Shuiping Yan (Fuel, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

Hydrogeological Control on Coalbed Methane Geochemistry in CO2/N2-Enriched Secondary Microbial Gas Areas: A Case Study in the Eastern Section of the Southern Junggar Basin, NW China - Baoxin Zhang; Ze Deng; Xuehai Fu; Yibing Wang; Longjiang Fan; Junqiang Kang; Zhenzhi Wang; Yanyan Ge (Natural Resources Research, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Metabarcoding reveals the differential sensitivity of planktonic microbiome to environmental filtering and biointeraction in Sansha Yongle blue hole - Tianying Chen; Yunyun Zhuang; Chang Chen; Xuewei Mao; Ruping Ge; Hongju Chen; Jianwei Chen; Liang Fu; Zuosheng Yang; Guangxing Liu (Frontiers in Marine Science, 2022)
The Sansha Yongle blue hole (SYBH) is the world’s deepest blue hole known so far and its unique hydrochemical characteristics make it a valuable site for studying biodiversity and ecological processes. Here, we used metabarcoding approach to investigate the diversity, assembly mechanism and co-occurrence pattern of planktonic microbiome in SYBH. Our results revealed the distinct separation of communities from upper oxic, middle oxic and suboxic-anoxic layer and significant day-night difference was detected in the upper-layer community of microeukaryotes, indicating potential diel migration. Stochastic processes played a significant role in the community assembly of microeukaryotes, while deterministic processes dominated in prokaryotes, confirming the stronger environmental filtering on prokaryotes as also suggested by the correlation with environmental variables. Microeukaryotes were less sensitive to environments but significantly affected by cross-domain biointeraction. When comparing the subcommunities of different abundance, we found that abundant taxa were widespread while rare taxa were habitat-specific. In co-occurrence network, over 87% of the interactions and 19 out of 20 keystone OTUs (Operational Taxonomic Units) were affiliated to moderate or rare taxa, suggesting the importance of non-abundant taxa in maintaining community stability. The predominant positive edges in the network pointed to that interspecies cooperation may be one of the ecological strategies in SYBH. Overall, we highlight the divergent assembly pattern and different driving forces in shaping plankton microbiome in SYBH, which may advance current understanding on diversity and dynamics of marine life in blue hole ecosystems.

Transport Patterns and Potential Sources of Atmospheric Pollution during the XXIV Olympic Winter Games Period - Yuting Zhang; Xiaole Pan; Yu Tian; Hang Liu; Xueshun Chen; Baozhu Ge; Zhe Wang; Xiao Tang; Shandong Lei; Weijie Yao; Yuanzhe Ren; Yongli Tian; et al. (Advances in Atmospheric Sciences, 2022)
The attainment of suitable ambient air quality standards is a matter of great concern for successfully hosting the XXIV Olympic Winter Games (OWG). Transport patterns and potential sources of pollutants in Zhangjiakou (ZJK) were investigated using pollutant monitoring datasets and a dispersion model. The PM 2.5 concentration during February in ZJK has increased slightly (28%) from 2018 to 2021, mostly owing to the shift of main potential source regions of west-central Inner Mongolia and Mongolian areas (2015–18) to the North China Plain and northern Shanxi Province (NCPS) after 2018. Using CO as an indicator, the relative contributions of the different regions to the receptor site (ZJK) were evaluated based on the source-receptor-relationship method (SRR) and an emission inventory. We found that the relative contribution of pollutants from NCPS increased from 33% to 68% during 2019–21. Central Inner Mongolia (CIM) also has an important impact on ZJK under unfavorable weather conditions. This study demonstrated that the effect of pollution control measures in the NCPS and CIM should be strengthened to ensure that the air quality meets the standard during the XXIV OWG.

Winter warming offsets one half of the spring warming effects on leaf unfolding - Huanjiong Wang; Junhu Dai; Josep Peñuelas; Quansheng Ge; Yongshuo H. Fu; Chaoyang Wu (Global Change Biology, 2022)
Winter temperature‐related chilling and spring temperature‐related forcing are two major environmental cues shaping the leaf‐out date of temperate species. To what degree insufficient chilling caused by winter warming would slow phenological responses to spring warming remains unclear. Using 27,071 time series of leaf‐out dates for 16 tree species in Europe, we constructed a phenological model based on the linear or exponential function between the chilling accumulation (CA) and forcing requirements (FR) of leaf‐out. We further used the phenological model to quantify the relative contributions of chilling and forcing on past and future spring phenological change. The results showed that the delaying effect of decreased chilling on the leaf‐out date was prevalent in natural conditions, as more than 99% of time series exhibited a negative relationship between CA and FR. The reduction in chilling linked to winter warming from 1951 to 2014 could offset about one half of the spring phenological advance caused by the increase in forcing. In future warming scenarios, if the same model is used and a linear, stable correlation between CA and FR is assumed, declining chilling will continuously offset the advance of leaf‐out to a similar degree. Our study stresses the importance of assessing the antagonistic effects of winter and spring warming on leaf‐out phenology.

Identification and validation of suitable reference genes for quantitative real-time PCR studies in Adiantum reniforme var. sinense - Qi Fu; Lin Xiang; Kai-ge Zhao; Long-qing Chen (Journal of Plant Biochemistry and Biotechnology, 2022)

Household solid fuel use with diabetes and fasting blood glucose levels among middle-aged and older adults in China - Yuxiong Chen; Siqin Feng; Zhen’ge Chang; Yakun Zhao; Jia Fu; Yijie Liu; Siqi Tang; Yitao Han; Yanbo Liu; Yuanxun Zhang; Shuyang Zhang; Zhongjie Fan (Environmental Science and Pollution Research, 2022)

Investigating the active compounds and mechanism of HuaShi XuanFei formula for prevention and treatment of COVID-19 based on network pharmacology and molecular docking analysis - Juan Wang; Wen Ge; Xin Peng; Lixia Yuan; Shuaibing He; Xuyan Fu (Molecular Diversity, 2022)

Strength variations due to re-liquefaction—indication from cyclic tests on undisturbed and remold samples of a liquefaction-recurring site - Fu-Kuo Huang; Chi-Chin Tsai; Louis Ge; Chih-Wei Lu; Chung-Chi Chi (Bulletin of Engineering Geology and the Environment, 2022)

A highly pathogenic Marek’s disease virus isolate from chickens immunized with a bivalent vaccine in China - Huimin Li; Zengxu Ge; Qiong Luo; Qiang Fu; Ruiai Chen (Archives of Virology, 2022)

Combined Effects of Microplastics and Benzo[a]pyrene on the Marine Diatom Chaetoceros muelleri - Yuanyuan Su; Huaiyuan Qi; Yipeng Hou; Mengyi Gao; Jie Li; Minggang Cai; Xiaoshan Zhu; Miao Chen; Chengjun Ge; Dongdong Fu; Zezheng Wang; Licheng Peng (Frontiers in Marine Science, 2022)
Microplastics are regarded as ubiquitous pollutants in the ocean and have attracted worldwide concerns. Benzo[a]pyrene (B[a]P), one of typical polycyclic aromatic hydrocarbons (PAHs), is commonly detected in marine environment. Once coexisted, the microplastics and B[a]P may interact with each other and result in combined toxicity to organisms, and these remain to be systematically elucidated. Thus, this study aims to investigate (i) the effects of single micro-sized polystyrene (mPS), polyethylene terephthalate (mPET), and B[a]P on cell growth of Chaetoceros muelleri ; and (ii) the interaction of microplastics and B[a]P, and their combined effects on C. muelleri . The results showed that both single microplastics and B[a]P at a high concentration of 150 μg/L inhibited the growth of C. muelleri . For single treatment of microplastics, stronger inhibition effects on microalgae was caused by mPET than that of mPS, with the highest IR of 25.23 and 11.17%, respectively. This may be attributed to the obvious surface roughness of mPET. By comparison, the combined effects of microplastics and B[a]P significantly inhibited the growth of C. muelleri as compared with the single treatment of B[a]P ( P < 0.05). Synergistic effect was found in the combination of microplastics with B[a]P at high concentrations of 150 μg/L. Interestingly, the antagonistic effect on C. muelleri was observed in the combined treatment of microplastics and B[a]P at low concentrations of 10 μg/L. In addition, the pollutants reduced the content of photosynthetic pigments in microalgal cells. The SOD and MDA content of microalgae increased in the early stage of exposure to pollutants (e.g., Days 1 and 5), but decreased in the later stage (Day 15) compared with the control group. The decreased superoxide dismutase (SOD) and catalase (CAT) activity in single and composite systems may indicate that the antioxidative enzymatic system of microalgae has been inhibited or destroyed. This study will be helpful to further explore the ecological threats of microplastics and PAHs to the marine ecosystem.

A study on the contamination assessment, health risk and mobility of two heavy metals in the soil-plants-ruminants system of a typical agricultural region in the semi arid environment - Xiaoping Ge; Zafar Iqbal Khan; Fu Chen; Mubeen Akhtar; Kafeel Ahmad; Abid Ejaz; Muhammad Arslan Ashraf; Muhammad Nadeem; Shahzad Akhtar; Jawaher Alkahtani; Yheni Dwiningsih; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Identification of key gene networks controlling vernalization development characteristics of Isatis indigotica by full-length transcriptomes and gene expression profiles - Pan Wang; Dong Liu; Fu-Hong Yang; Hui Ge; Xin Zhao; Hong-Gang Chen; Tao Du (Physiology and Molecular Biology of Plants, 2021)
Isatis indigotica Fort . , as a common Chinese medicinal raw material, will lose its medicinal value if it blooms early, so it is highly valuable to clarify the induction mechanism of the vernalization of I. indigotica at low temperature. In this study, the concentrations of soluble sugar, proline, glutathione and zeatin in two germplasms of I. indigotica with different degrees of low temperature tolerance (Y1 and Y2) were determined at 10 days, 20 days and 30 days of low-temperature treatment, and the full-length transcriptome of 24 samples was sequenced by Nanopore sequencing with Oxford Nanopore Technologies (ONT). After that, the data of transcripts involved in the vernalization of I. indigotica at low temperature were obtained, and these transcripts were identified using weighted gene co-expression network analysis (WGCNA). The results revealed the massive accumulation of soluble sugar and proline in Y1 and Y2 after low temperature induction. A total of 18,385 new transcripts, 6168 transcription factors and 470 lncRNAs were obtained. Differential expression analysis showed that gibberellin, flavonoids, fatty acids and some processes related to low temperature response were significantly enriched. Eight key transcripts were identified by WGCNA, among which ONT.14640.1, ONT.9119.1, ONT.13080.2 and ONT.16007.1 encodes a flavonoid transporter, 9-cis-epoxycarotenoid dioxygenase 3 (NCED3), growth factor gene and L-aspartate oxidase in plants, respectively . It indicated that secondary metabolites such as hormones and flavonoids play an important role in the vernalization of I. indigotica . qRT-PCR proved the reliability of transcriptome results. These results provide important insights on the low-temperature vernalization of I. indigotica , and provide a research basis for analyzing the vernalization mechanism of I. indigotica .

Adsorption Removal of Phosphate and Fluoride from Aqueous Solution Using Oily Sludge-based Pyrolysis Residue - Huifen Yang; Peng Fu; Ge Zhang; Qingping Zhang; Xuan Li (Environmental Processes, 2021)

Evaluation of pasture allowance of manganese for ruminants - Xiaoping Ge; Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Mudasra Munir; Muhammad Nadeem; Muhammad Umer Farooq Awan; et al. (Environmental Science and Pollution Research, 2021)

Developing urinary pyrrole–amino acid adducts as non-invasive biomarkers for identifying pyrrolizidine alkaloids-induced liver injury in human - Lin Zhu; Chunyuan Zhang; Wei Zhang; Qingsu Xia; Jiang Ma; Xin He; Yisheng He; Peter P. Fu; Wei Jia; Yuzheng Zhuge; Ge Lin (Archives of Toxicology, 2021)

Aestuariibaculum sediminum sp. nov., a marine bacterium isolated from a tidal flat in Zhoushan - Zhi-Cheng Wu; Xin-Yin Zhang; Cong Sun; Lin Xu; Ge-Yi Fu; Xue-Wei Xu (Archives of Microbiology, 2021)

Estimations of Land Surface Characteristic Parameters and Turbulent Heat Fluxes over the Tibetan Plateau Based on FY-4A/AGRI Data - Nan Ge; Lei Zhong; Yaoming Ma; Yunfei Fu; Mijun Zou; Meilin Cheng; Xian Wang; Ziyu Huang (Advances in Atmospheric Sciences, 2021)

Biochar decreased rhizodeposits stabilization via opposite effects on bacteria and fungi: diminished fungi-promoted aggregation and enhanced bacterial mineralization - Zhiyi Chen; Amit Kumar; Yingyi Fu; Bhupinder Pal Singh; Tida Ge; Hua Tu; Yu Luo; Jianming Xu (Biology and Fertility of Soils, 2021)

B3GNT3 acts as a carcinogenic factor in endometrial cancer via facilitating cell growth, invasion and migration through regulating RhoA/RAC1 pathway-associated markers - Ji-Shui Wang; Fang Ruan; Li-Zhu Guo; Feng-Ge Wang; Fu-Ling Wang; Hong-Min An (Genes & Genomics, 2021)

Effect of clonal fragmentation on the growth of Vallisneria natans (Lour.) Hara at contrasting nutrient and light conditions - Hui Peng; Dabing Ge; Guixiang Yuan; Dongsheng Zou; Hui Fu; Erik Jeppesen (Hydrobiologia, 2021)

Genetic variants in N6-methyladenosine are associated with bladder cancer risk in the Chinese population - Hanting Liu; Jingjing Gu; Yu Jin; Qi Yuan; Gaoxiang Ma; Mulong Du; Yuqiu Ge; Chao Qin; Qiang Lv; Guangbo Fu; Meilin Wang; Haiyan Chu; et al. (Archives of Toxicology, 2021)

Identifying the sources of seasonal predictability based on climate memory analysis and variance decomposition - Da Nian; Naiming Yuan; Kairan Ying; Ge Liu; Zuntao Fu; Yanjun Qi; Christian L. E. Franzke (Climate Dynamics, 2020)

Bearing performance of offshore bucket foundation with internal cruciform skirt under combined loading - Zhong Xiao; Ying Liu; Borui Ge; Dengfeng Fu; Zengfeng Zhou; Yue Yan (Marine Georesources & Geotechnology, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Removal of nitrate nitrogen from water by phosphotungstate-supported TiO2 photocatalytic method - Xiaohong Ge; Weizhang Fu; Yujun Wang; Lingsheng Wang; Fanfeng Yao (Environmental Science and Pollution Research, 2020)

Post-Orogenic Tectonic Evolution of the Jiangnan-Xuefeng Orogenic Belt: Insights from Multiple Geochronometric Dating of the Mufushan Massif, South China - Chuanbo Shen; Di Hu; Kyoungwon Min; Chaoqun Yang; Xiaowei Zeng; Hongyang Fu; Xiang Ge (Journal of Earth Science, 2020)

Tunneling-induced deep-seated landslides: a case study in Gulin County, Sichuan, China - Zhong Fu Wang; Feng Ge Shi; Dong Dong Li; Haoyuan Li (Arabian Journal of Geosciences, 2020)

Phosphorus supply via a fed-batch strategy improves lipid heterotrophic production of Chlorella regularis - Liang Fu; Ge Yan; Yunbao Li; Qingcheng Li; Dandan Zhou (Environmental Science and Pollution Research, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Associations between geographical environment and systolic pulmonary arterial pressure of Chinese adults: impact analysis and predictive modeling - Xinlei Liu; Chunqi Li; Hao Fu; Xuxiang Li; Miao Ge (International Journal of Biometeorology, 2020)

Possible aerosol transmission of COVID-19 and special precautions in dentistry - Zi-yu Ge; Lu-ming Yang; Jia-jia Xia; Xiao-hui Fu; Yan-zhen Zhang (Journal of Zhejiang University-SCIENCE B, 2020)

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

Cascading effects of elevation, soil moisture and soil nutrients on plant traits and ecosystem multi-functioning in Poyang Lake wetland, China - Hui Fu; Guixiang Yuan; Dabing Ge; Wei Li; Dongsheng Zou; Zhenrong Huang; Aiping Wu; Qiaolin Liu; Erik Jeppesen (Aquatic Sciences, 2020)

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

In-Situ Immobilization of Cd-Contaminated Soils Using Ferronickel Slag as Potential Soil Amendment - Pingfeng Fu; Huifen Yang; Ge Zhang; Peng Fu; Zhaofeng Li (Bulletin of Environmental Contamination and Toxicology, 2019)

3D-Printed Wearable Personalized Orthodontic Retainers for Sustained Release of Clonidine Hydrochloride - Heliu Jiang; Junhui Fu; Mingguang Li; Shanshan Wang; Bo Zhuang; Haiyan Sun; Cheng Ge; Bin Feng; Yiguang Jin (AAPS PharmSciTech, 2019)

Intestinal and hepatic biotransformation of pyrrolizidine alkaloid N-oxides to toxic pyrrolizidine alkaloids - Mengbi Yang; Jiang Ma; Jianqing Ruan; Yang Ye; Peter Pi-Cheng Fu; Ge Lin (Archives of Toxicology, 2019)

Multi-GNSS real-time clock estimation using sequential least square adjustment with online quality control - Wenju Fu; Guanwen Huang; Qin Zhang; Shengfeng Gu; Maorong Ge; Harald Schuh (Journal of Geodesy, 2019)

Identification, evolution and alternative splicing profile analysis of the splicing factor 30 (SPF30) in plant species - Di Zhang; Jing-Fang Yang; Bei Gao; Tie-Yuan Liu; Ge-Fei Hao; Guang-Fu Yang; Li-Jun Fu; Mo-Xian Chen; Jianhua Zhang (Planta, 2019)

Increased fes1a thermotolerance is induced by BAG6 knockout - Can Fu; Yanfei Hou; Jingjing Ge; Limin Zhang; Xiaxia Liu; Panfei Huo; Jian Liu (Plant Molecular Biology, 2019)

Refining ionospheric delay modeling for undifferenced and uncombined GNSS data processing - Qile Zhao; YinTong Wang; Shengfeng Gu; Fu Zheng; Chuang Shi; Maorong Ge; Harald Schuh (Journal of Geodesy, 2019)

Genome-wide identification and functional analysis of the splicing component SYF2/NTC31/p29 across different plant species - Yuan Tian; Mo-Xian Chen; Jing-Fang Yang; H. H. K. Achala; Bei Gao; Ge-Fei Hao; Guang-Fu Yang; Zhi-Yong Dian; Qi-Juan Hu; Di Zhang; Jianhua Zhang; Ying-Gao Liu (Planta, 2019)

The role of formation of pyrrole–ATP synthase subunit beta adduct in pyrrolizidine alkaloid-induced hepatotoxicity - Yao Lu; Jiang Ma; Zijing Song; Yang Ye; Peter P. Fu; Ge Lin (Archives of Toxicology, 2018)

The relative abundance of alkane‐degrading bacteria oscillated similarly to a sinusoidal curve in an artificial ecosystem model from oil‐well products - Guoqiang Li; Peike Gao; Bo Zhi; Bing Fu; Ge Gao; Zhaohui Chen; Mengli Gao; Mengmeng Wu; Ting Ma (Environmental Microbiology, 2018)
Summary Microbial phylogenetic diversity and species interactions in natural ecosystems have been investigated extensively, but our knowledge about their ecological roles, community dynamics and succession patterns is far from complete. This knowledge is essential to understand the complicated interactions of microorganisms in natural ecosystems. Here, an artificial ecosystem model of microorganisms was constructed from oil‐well products and cultivated in a chemostat to investigate the succession pattern of alkane‐degrading bacteria, a functional population in oil reservoirs. Their abundance was quantified by an improved qPCR technique. Our results showed that the phylogenetic structure of this artificial ecosystem model is stable during most of the chemostat cultivation process, while the genotype structure of alkane‐degrading bacteria containing alk B genes shifted and their relative abundance oscillated similarly to a sinusoidal curve, like the succession pattern of producers in the Lotka–Volterra model. These results suggest that some theoretical frameworks of macroecology may work well in microbial ecosystems and be an efficient tool to understand them.

An efficient solution of real-time data processing for multi-GNSS network - Xiaopeng Gong; Shengfeng Gu; Yidong Lou; Fu Zheng; Maorong Ge; Jingnan Liu (Journal of Geodesy, 2018)

Spatio-temporal simulation of the geopolitical environment system - Quansheng Ge; Dong Jiang; Feng Lu; Jingying Fu; Shaoqiang Wang; Xiangzheng Deng (Journal of Geographical Sciences, 2018)

Isotope Chronology and Geochemistry of the Lower Carboniferous Granite in Xilinhot, Inner Mongolia, China - Xiaocheng Zhao; Wenxiao Zhou; Dong Fu; Bo Huang; Mengchun Ge (Journal of Earth Science, 2018)

Re–Os geochronology of the Cambrian stage-2 and -3 boundary in Zhijin County, Guizhou Province, China - Shuaichao Wei; Yong Fu; Houpeng Liang; Zhihua Ge; Wenxi Zhou; Guangzhe Wang (Acta Geochimica, 2018)

Colletotrichum atractylodicola sp. nov.: the anthracnose pathogen of Atractylodes chinensis in China - Haijiao Xu; Rujun Zhou; Junfan Fu; Yue Yuan; Xinxin Ge; Ulrike Damm (Mycological Progress, 2018)

Interaction network of core ABA signaling components in maize - Ying-Ge Wang; Feng-Ling Fu; Hao-Qiang Yu; Tao Hu; Yuan-Yuan Zhang; Yi Tao; Jian-Kang Zhu; Yang Zhao; Wan-Chen Li (Plant Molecular Biology, 2018)

Aestuarium zhoushanense gen. nov., sp. nov., Isolated from the Tidal Flat - Xiao-Yun Yu; Jing-Yu Zhai; Ge-Yi Fu; Xia Shen; Zhe Zhao; Min Wu; Xin-Qi Zhang (Current Microbiology, 2017)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

Artepillin C, is it a good marker for quality control of Brazilian green propolis? - Cui-ping Zhang; Xiao-ge Shen; Jia-wei Chen; Xia-sen Jiang; Kai Wang; Fu-liang Hu (Natural Product Research, 2017)

Deletion of mammalian sterile 20-like kinase 1 attenuates neuronal loss and improves locomotor function in a mouse model of spinal cord trauma - Pan-feng Wang; Da-yuan Xu; Yuntong Zhang; Xiao-bin Liu; Yan Xia; Pan-yu Zhou; Qing-ge Fu; Shuo-gui Xu (Molecular and Cellular Biochemistry, 2017)

Diurnal variations of carbon dioxide, methane, and nitrous oxide fluxes from invasive Spartina alterniflora dominated coastal wetland in northern Jiangsu Province - Xinwanghao Xu; Guanghe Fu; Xinqing Zou; Chendong Ge; Yifei Zhao (Acta Oceanologica Sinica, 2017)

The long persistence of pyrrolizidine alkaloid-derived DNA adducts in vivo: kinetic study following single and multiple exposures in male ICR mice - Lin Zhu; Junyi Xue; Qingsu Xia; Peter P. Fu; Ge Lin (Archives of Toxicology, 2017)

Research on sequence stratigraphy, hydrogeological units and commingled drainage associated with coalbed methane production: a case study in Zhuzang syncline of Guizhou province, China - Xin Li; Xuehai Fu; Yanyan Ge; Xixi Chang (Hydrogeology Journal, 2016)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Intein-mediated Cre protein assembly for transgene excision in hybrid progeny of transgenic Arabidopsis - Jia Ge; Lijun Wang; Chen Yang; Lingyu Ran; Mengling Wen; Xianan Fu; Di Fan; Keming Luo (Plant Cell Reports, 2016)

Role of methylenetetrahydrofolate reductase 677C→T polymorphism in the development of myocardial infarction: evidence from an original study and updated meta-analysis - Wenbin Zhang; Min Wang; Pei Zhang; Zhimin Xue; Guosheng Fu; Junbo Ge; Yi Luan (Genes & Genomics, 2016)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Cloning and Characterization of a Pyruvate Carboxylase Gene from Penicillium rubens and Overexpression of the Genein the Yeast Yarrowia lipolytica for Enhanced Citric Acid Production - Ge-Yi Fu; Yi Lu; Zhe Chi; Guang-Lei Liu; Shou-Feng Zhao; Hong Jiang; Zhen-Ming Chi (Marine Biotechnology, 2016)

Cardioprotective Effect of Anisodamine Against Myocardial Ischemia Injury and its Influence on Cardiomyocytes Apoptosis - Kun Xing; Xianghua Fu; Lingling Jiang; Yanbo Wang; Wei Li; Xinshun Gu; Guozhen Hao; Qing Miao; Xiaolin Ge; Yuhong Peng; Wei Geng; Shiru Bai; et al. (Cell Biochemistry and Biophysics, 2015)

Production of sweet orange somaclones tolerant to citrus canker disease by in vitro mutagenesis with EMS - Hongjuan Ge; Yi Li; Hongyan Fu; Guiyou Long; Li Luo; Ronghua Li; Ziniu Deng (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Hydrotubation Combined with Chinese Herbal Medicine for Salpingitic Infecundity: A Systematic Review and Meta-Analysis - Huanhuan Wen; Jinrong Fu; Hong Tang; Man Ge; Linna Feng (Cell Biochemistry and Biophysics, 2015)

Expression Profile of Maize MicroRNAs Corresponding to Their Target Genes Under Drought Stress - Ying-Ge Wang; Ming An; Shu-Feng Zhou; Yue-Hui She; Wan-Chen Li; Feng-Ling Fu (Biochemical Genetics, 2014)

miR-210 over-expression enhances mesenchymal stem cell survival in an oxidative stress environment through antioxidation and c-Met pathway activation - JianFeng Xu; ZheYong Huang; Li Lin; MingQiang Fu; YanHua Gao; YunLi Shen; YunZeng Zou; AiJun Sun; JuYing Qian; JunBo Ge (Science China Life Sciences, 2014)

Phenotypic characterization of craniofacial bone marrow stromal cells: unique properties of enhanced osteogenesis, cell recruitment, autophagy, and apoptosis resistance - Weijie Dong; Jie Ge; Ping Zhang; Yu Fu; Ziwen Zhang; Jie Cheng; Hongbing Jiang (Cell and Tissue Research, 2014)

Serum microRNA-195 is down-regulated in breast cancer: a potential marker for the diagnosis of breast cancer - Fu-long Zhao; Yue-chao Dou; Xue-fei Wang; Da-cheng Han; Zhen-gang LV; Shuang-lei Ge; Ya-kui Zhang (Molecular Biology Reports, 2014)

Comparative genotype reactions to Sclerotinia sclerotiorum within breeding populations of Brassica napus and B. juncea from India and China - M. J. Barbetti; S. K. Banga; T. D. Fu; Y. C. Li; D. Singh; S. Y. Liu; X. T. Ge; S. S. Banga (Euphytica, 2014)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

An integrated East China Sea–Changjiang Estuary model system with aim at resolving multi-scale regional–shelf–estuarine dynamics - Jianzhong Ge; Pingxing Ding; Changsheng Chen; Song Hu; Gui Fu; Lunyu Wu (Ocean Dynamics, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

RNA interference-mediated resistance to maize dwarf mosaic virus - Zhi-Yong Zhang; Ying-Ge Wang; Xiao-Juan Shen; Lei Li; Shu-Feng Zhou; Wan-Chen Li; Feng-Ling Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

High density lipoprotein cholesterol promotes the proliferation of bone-derived mesenchymal stem cells via binding scavenger receptor-B type I and activation of PI3K/Akt, MAPK/ERK1/2 pathways - Jianfeng Xu; Juying Qian; Xinxing Xie; Li Lin; Jianying Ma; Zheyong Huang; Mingqiang Fu; Yunzeng Zou; Junbo Ge (Molecular and Cellular Biochemistry, 2012)

An enormous Jurassic turtle bone bed from the Turpan Basin of Xinjiang, China - Oliver Wings; Márton Rabi; Jörg W. Schneider; Leonie Schwermann; Ge Sun; Chang-Fu Zhou; Walter G. Joyce (The Science of Nature, 2012)

Norcantharidin, a protective therapeutic agent in renal tubulointerstitial fibrosis - Ying Li; Yan Ge; Fu You Liu; You Ming Peng; Lin Sun; Jun Li; Qiong Chen; Yan Sun; Kun Ye (Molecular and Cellular Biochemistry, 2012)

Greening China Naturally - Shixiong Cao; Ge Sun; Zhiqiang Zhang; Liding Chen; Qi Feng; Bojie Fu; Steve McNulty; David Shankman; Jianwu Tang; Yanhui Wang; Xiaohua Wei (Ambio, 2011)

Spectroscopic and Molecular Modeling Studies on the Interaction Between a Fluorine-Containing Triazole Derivative and Human Serum Albumin - Jia-Xin Fu; Yu-Shu Ge; Feng-Lei Jiang; Xiao-Hong Sun; Yang Liu; Yi Liu (Biological Trace Element Research, 2011)

Downregulation of Cinnamyl Alcohol Dehydrogenase (CAD) Leads to Improved Saccharification Efficiency in Switchgrass - Chunxiang Fu; Xirong Xiao; Yajun Xi; Yaxin Ge; Fang Chen; Joseph Bouton; Richard A. Dixon; Zeng-Yu Wang (BioEnergy Research, 2011)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Agrobacterium-Mediated Transformation of Switchgrass and Inheritance of the Transgenes - Yajun Xi; Chunxiang Fu; Yaxin Ge; Rangaraj Nandakumar; Hiroshi Hisano; Joseph Bouton; Zeng-Yu Wang (BioEnergy Research, 2009)

Ischemic preconditioning induces chaperone hsp70 expression and inhibits protein aggregation in the CA1 neurons of rats - Peng-Fei Ge; Tian-Fei Luo; Ji-Zhou Zhang; Da-Wei Chen; Yong-Xin Luan; Shuang-Lin Fu (Neuroscience Bulletin, 2008)

No Correlation Between Heterozygosity and Vegetative Fitness in the Narrow Endemic and Critically Endangered Clematis acerifolia (Ranunculaceae) - Jordi López-Pujol; Fu-Min Zhang; Song Ge (Biochemical Genetics, 2008)

One new cinnamic imide dervative from the fruits of Tribulus terrestris - A-Li Lv; Nan Zhang; Min-Ge Sun; Yong-Fu Huang; Yi Sun; Hong-Yu Ma; Hui-Ming Hua; Yue-Hu Pei (Natural Product Research, 2008)

Areas of endemism and patterns of diversity for aphids of the Qinghai‐Tibetan Plateau and the Himalayas - Xiao‐Lei Huang; Fu‐Min Lei; Ge‐Xia Qiao (Journal of Biogeography, 2008)
Aim The study aimed to identify areas of endemism for aphids in the Qinghai‐Tibetan Plateau and the Himalayas (QTPH), and to test congruence between patterns of endemism and patterns of overall species richness identified in a previous study. Location The QTPH. Methods A distribution data base of 326 endemic aphids in the QTPH was compiled. The study area was divided into a grid of 2°× 2° operative geographical units. Parsimony analysis of endemicity (PAE) was used to identify areas of endemism, and the diversity patterns of endemic species were then mapped using GIS. Results We identified 326 endemic species belonging to 138 genera within Adelgidae and 14 subfamilies of Aphididae. Five areas of endemism were found using PAE analysis: the eastern Himalayas, the western Himalayas, north‐western Yunnan, southern Tibet and the eastern QTPH. Maps of patterns of endemism identified four major centres for endemic aphids, namely the western Himalayas, the eastern Himalayas (or Sikkim‐Assam Himalayas), north‐western Hengduan Mountains and the mountains of southern Gansu Province, and three minor centres, southern Tibet, south‐eastern Tibet and the eastern Qinghai Province in the north‐eastern QTPH. Main conclusions Our study identifies major centres of aphid endemism. Furthermore, there is a noticeable congruence between patterns of endemism and patterns of species richness. The patterns of endemism were most likely influenced by the recent uplift of the QTPH.

Isolation and characterization of a novel cDNA encoding ERF/AP2-type transcription factor OsAP25 from Oryza Sativa L. - Xiao-Yan Fu; Zhen Zhang; Ri-He Peng; Ai-Sheng Xiong; Jin-Ge Liu; Li-Juan Wu; Feng Gao; Hong Zhu; Zhao-Kui Guo; Quan-Hong Yao (Biotechnology Letters, 2007)

Screen p53 mutations in hepatocellular carcinoma by FASAY: A novel splicing mutation - Xiao-mo Wu; Jing-geng Fu; Wang-zhong Ge; Jiang-yan Zhu; Jun-yong Wang; Wei Zhang; Wei Qian; Ke-ke Huo (Journal of Zhejiang University-SCIENCE B, 2007)

Plant Biodiversity in China: Richly Varied, Endangered, and in Need of Conservation - Jordi López-Pujol; Fu-Min Zhang; Song Ge (Biodiversity and Conservation, 2006)

FPF1 transgene leads to altered flowering time and root development in rice - Ming-Li Xu; Jia-Fu Jiang; Lei Ge; Yun-Yuan Xu; Hui Chen; Yuan Zhao; Yu-Rong Bi; Jiang-Qi Wen; Kang Chong (Plant Cell Reports, 2005)

Adult-Plant Resistance to Powdery Mildew in Knox 62 Wheat - J. W. Johnson; Yong-fu Ge; J. J. Roberts; P. Raymer; Yong Seo (Cereal Research Communications, 2003)

The relationship between human cytomegalovirus infection and atherosclerosis development - Ruizhen Chen; Sidong Xiong; Yingzhen Yang; Weiguo Fu; Yuqi Wang; Junbo Ge (Molecular and Cellular Biochemistry, 2003)

Temperature and resistance gene interactions in the expression of resistance to Blumeria Graminis f. sp. Tritici - Yong-fu Ge; W. Johnson; John J. Roberts; S. Rajaram (Euphytica, 1998)